Toner and method for producing toner
A toner with a crystalline and non-crystalline resin domain-matrix structure, enhanced by specific acid values and polyvalent metal elements, addresses fixability and resistance issues, ensuring stable performance in varying environmental conditions.
Patent Information
- Application Number
- CN202011459163.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-13
- Filing Date
- 2020-12-11
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2040-12-11
AI Technical Summary
Existing toners face challenges in achieving both low-temperature fixability, hot offset resistance, and winding resistance, particularly in high-temperature and high-humidity environments, with crystalline resins like crystalline polyesters and vinyl resins exhibiting poor charging stability and viscosity issues.
A toner composition comprising a binder resin with a domain-matrix structure formed by a crystalline resin and a non-crystalline resin, along with specific acid values and polyvalent metal elements, such as Mg, Ca, Al, and Zn, to enhance dispersion and interaction, resulting in improved fixing performance.
The toner achieves excellent low-temperature fixability, hot offset resistance, and winding resistance, maintaining charging stability even in high-temperature and high-humidity conditions.
Smart Images

Figure BDA0002830676770000031 
Figure BDA0002830676770000041 
Figure BDA0002830676770000061
Abstract
Description
Technical Field
[0001] The present disclosure relates to a toner used for an electrophotographic system, an electrostatic recording system, an electrostatic printing system, and the like, and to a method for producing the toner. Background Art
[0002] With the popularity of full-color electrophotographic copiers in recent years, there has been an increasing demand for high-speed printing and high energy saving. In order to achieve high-speed printing, a technology for melting toner more quickly in the fixing step has been studied. A technology for shortening various control times within and between jobs has been studied to improve productivity. As an energy-saving strategy, a technology for fixing toner at low temperatures has been studied to reduce energy consumption in the fixing step.
[0003] It is known that when a crystalline resin having a rapid melting property is used as a main component of a binder resin in a toner, the toner has a more excellent low-temperature fixability than a toner having a non-crystalline resin as a main component. Many toners have been proposed, which contain a crystalline polyester as a resin having a rapid melting property. However, crystalline polyesters are problematic in terms of charging stability in a high-temperature and high-humidity environment, and particularly in terms of maintaining charging performance after being left in a high-temperature and high-humidity environment.
[0004] Various toners have also been proposed which use a crystalline vinyl resin as another kind of crystalline resin having a sharp melt property.
[0005] For example, Japanese Patent Application Publication No. 2014-130243 proposes a toner that achieves both low-temperature fixability and heat-resistant storage stability by using an acrylate resin having crystallinity in a side chain.
[0006] The toner of the above patent document can provide both low-temperature fixability and heat-resistant storage stability, and can also provide a certain degree of improvement in charging stability, which has been a weak point of the toner using a crystalline polyester resin. However, it has been found that since the viscosity of the toner using a crystalline vinyl resin as a binder resin is too low in a high temperature region, it is prone to hot offset and winding and has a narrow fixing temperature range.
[0007] Therefore, research has been conducted on adding a non-crystalline resin to a crystalline resin to increase the viscosity after the toner is melted.
[0008] For example, WO 2019 / 073731 proposes a toner using a binder resin in which a crystalline vinyl resin and a polyester resin cross-linked by a carbon-carbon bond are combined. Summary of the invention
[0009] However, it has been found that although the toner of WO 2019 / 073731 ensures the fixing range to a certain extent, further improvement is still needed.
[0010] The present disclosure provides a toner that simultaneously achieves excellent low-temperature fixability, hot offset resistance, and winding resistance, and provides a method for producing the toner.
[0011] One aspect of the present disclosure is to provide a toner including toner particles containing a binder resin including a first resin and a second resin, wherein
[0012] The first resin is a crystalline resin,
[0013] The second resin is a non-crystalline resin,
[0014] The first resin has a first monomer unit represented by the following formula (1),
[0015] The content ratio of the first monomer unit in the first resin is 30.0 mass % to 99.9 mass %,
[0016] The acid value of the first resin is 0.1 mg KOH / g to 30 mg KOH / g,
[0017] The acid value of the second resin is 0.5 mg KOH / g to 40 mg KOH / g,
[0018] A domain-matrix structure formed by a matrix containing the first resin and a domain containing the second resin appears in cross-sectional observation of the toner,
[0019] The toner particles further contain a polyvalent metal element,
[0020] The polyvalent metal element is at least one metal element selected from the group consisting of Mg, Ca, Al, Fe and Zn, and
[0021] The total content of the polyvalent metal element is 0.0025 parts by mass to 3.0000 parts by mass relative to 100 parts by mass of the binder resin:
[0022] In formula (1), R Z1 represents a hydrogen atom or a methyl group, and R represents C 18-36 alkyl.
[0023] Another aspect of the present disclosure provides a method for manufacturing a toner, the method comprising:
[0024] a step of preparing a dispersion of fine resin particles containing a binder resin;
[0025] a step of adding a coagulant to the resin fine particle dispersion to form aggregated particles; and
[0026] a step of heating and fusing the aggregated particles to obtain a dispersion containing toner particles, wherein
[0027] The binder resin includes a first resin and a second resin,
[0028] The first resin is a crystalline resin,
[0029] The second resin is a non-crystalline resin,
[0030] The first resin has a first monomer unit represented by the following formula (1),
[0031] The content ratio of the first monomer unit in the first resin is 30.0 mass % to 99.9 mass %,
[0032] The acid value of the first resin is 0.1 mg KOH / g to 30 mg KOH / g,
[0033] The acid value of the second resin is 0.5 mg KOH / g to 40 mg KOH / g,
[0034] A domain-matrix structure formed by a matrix containing the first resin and a domain containing the second resin appears in cross-sectional observation of the toner,
[0035] The toner particles further contain a polyvalent metal element,
[0036] The polyvalent metal element is at least one metal element selected from the group consisting of Mg, Ca, Al, Fe and Zn, and
[0037] The total content of the polyvalent metal element is 0.0025 parts by mass to 3.0000 parts by mass relative to 100 parts by mass of the binder resin:
[0038] In formula (1), R Z1 represents a hydrogen atom or a methyl group, and R represents C 18-36 alkyl.
[0039]
[0040] The present disclosure provides a toner that simultaneously achieves excellent low-temperature fixability, hot offset resistance, and wrapping resistance.
[0041] Further features of the present invention will become apparent from the following description of exemplary embodiments. DETAILED DESCRIPTION
[0042] Unless otherwise stated, the expression of a numerical range in the present disclosure such as "from XX to YY" or "XX to YY" includes the numerical range of the upper and lower limits of the range.
[0043] In the present disclosure, (meth)acrylate refers to acrylate and / or methacrylate.
[0044] When a numerical range is described in steps, the respective upper and lower limits of each numerical range can be arbitrarily combined.
[0045] The term "monomer unit" describes the reacted form of a monomer material in a polymer. For example, a carbon-carbon bonded segment in the backbone of a polymerized vinyl monomer in a polymer is taken as a unit. A vinyl monomer can be represented by the following formula (Z):
[0046]
[0047] [In formula (Z), R Z1 represents a hydrogen atom or an alkyl group (preferably C 1-3 alkyl, or more preferably methyl), and R Z2 represents any substituent].
[0048] The crystalline resin is a resin that shows a clear endothermic peak in differential scanning calorimetry (DSC) measurement.
[0049] The inventors believe that these effects are achieved by the following mechanism.
[0050] The melting characteristics and fixing performance of toner are considered to be determined by the domain-matrix structure in the binder resin inside the toner particles. Conventionally, it is known that the melting properties of toner can be controlled by mixing crystalline resin with non-crystalline resin to obtain rapid melting viscoelasticity and improve elasticity in the high temperature region.
[0051] However, the inventors' research has shown that when a crystalline vinyl resin having strong rapid melting properties is used as a matrix of a domain-matrix structure in a binder resin, the dispersion state of the domains formed by the non-crystalline resin is not ideal, and the fixing performance is actually reduced. This is attributed to the poor dispersion of the domains of the non-crystalline resin, which results in excessively large domains.
[0052] Studies on changing the composition of the binder resin have shown that fixing performance is slightly improved by using a crystalline resin containing a monomer having an acid value such as an ester group. However, some compositions have reduced low-temperature fixing property or hot offset resistance.
[0053] Then, as a result of intensive studies by the inventors, it was found that these problems can be solved by controlling the acid value of the crystalline resin and the acid value of the non-crystalline resin and the content of the polyvalent metal element in the toner within specific ranges.
[0054] In these disclosures, a domain-matrix structure composed of a matrix containing a first resin as a crystalline resin and a domain containing a second resin as a non-crystalline resin appears in cross-sectional observation of the toner. When such a domain-matrix structure is formed, both low-temperature fixability and hot offset resistance can be achieved.
[0055] The first resin is a crystalline resin having a first monomer unit represented by formula (1).
[0056] The content ratio of the first monomer unit in the first resin is 30.0 mass % to 99.9 mass %. The acid value of the first resin is 0.1 mg KOH / g to 30 mg KOH / g. Since the first resin has such a first monomer unit, the binder resin has crystallinity and the low temperature fixability of the toner is improved.
[0057] When the content ratio of the first monomer unit in the first resin is 30.0% by mass to 99.9% by mass, low-temperature fixability and fixation separation properties are good.
[0058] If the content ratio of the first monomer unit is less than 30.0 mass %, low temperature fixability is reduced. The range is more preferably 40.0 mass % to 90.0 mass %, or still more preferably 45.0 mass % to 75.0 mass %. If the content ratio of the first monomer unit exceeds 99.9 mass %, since too much of the first resin can be occupied by the non-polar part having a low SP value, the fixation separation property can be reduced.
[0059] The acid value of the first resin (crystalline resin) is 0.1 mg KOH / g to 30 mg KOH / g. If the acid value is within this range, low temperature fixability and hot offset resistance are improved because the first resin and the polyvalent metal element interact more easily, or in other words, because ionic crosslinking of the resin by the polyvalent metal element occurs more easily, and the dispersibility of the domain of the second resin can be improved more easily.
[0060] If the acid value of the first resin is less than 0.1 mg KOH / g, these effects are not obtained. If the acid value of the first resin exceeds 30 mg KOH / g, the charge maintenance performance in a high humidity environment may be reduced and fogging may occur, especially because the hydrophobicity of the toner particle surface is reduced. A more preferred range is 5 mg KOH / g to 15 mg KOH / g.
[0061]
[0062] [In formula (1), R Z1 represents a hydrogen atom or a methyl group, and R represents C 18-36 Alkyl (preferably C 18-30 Straight chain alkyl).]
[0063] The first monomer unit represented by formula (1) is preferably derived from a monomer selected from the group consisting of 18-36 At least one of the group consisting of alkyl (meth)acrylates.
[0064] With C 18-36 Examples of alkyl (meth)acrylates include 18-36 (Meth)acrylates of linear alkyl groups [stearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, heneicosyl (meth)acrylate, behenyl (meth)acrylate, wood wax (meth)acrylate, hexadecyl (meth)acrylate, dioctadecyl (meth)acrylate, myricyl (meth)acrylate, tridecyl (meth)acrylate, etc.] and those having C 18-36 Branched alkyl (meth)acrylate [2-decyltetradecyl (meth)acrylate, etc.].
[0065] Among them, from the viewpoint of low temperature fixing property, charging rise performance and charging stability of the toner, it is preferable to select 18-36 At least one of (meth)acrylates of linear alkyl groups, more preferably selected from 18-30 At least one kind of linear alkyl (meth)acrylate, and still more preferably at least one kind selected from linear stearyl (meth)acrylate and behenyl (meth)acrylate.
[0066] A single monomer or a combination of at least two monomers may be used to form the first monomer unit.
[0067] The first resin is preferably a vinyl polymer. The vinyl polymer may be, for example, a polymer of a monomer containing an ethylenically unsaturated bond. The ethylenically unsaturated bond is a free radical polymerizable carbon-carbon double bond, and examples include vinyl, propylene, acryloyl, methacryloyl, and the like.
[0068] The first resin preferably has a second monomer unit which is different from the first monomer unit and is at least one selected from the group consisting of a monomer unit represented by the following formula (2) and a monomer unit represented by the following formula (3).
[0069] The content ratio of the second monomer unit in the first resin is preferably 1.0% by mass to 70.0% by mass, or more preferably 10.0% by mass to 60.0% by mass, or still more preferably 15.0% by mass to 30.0% by mass.
[0070]
[0071] (In formula (2), X represents a single bond or C 1-6 Alkylene,
[0072] R 1represents a nitrile group (-C≡N),
[0073] Amide (-C(=O)NHR 10 (where R 10 Represents a hydrogen atom or C 1-4 alkyl)),
[0074] Hydroxyl,
[0075] -COOR 11 (where R 11 Represents C 1-6 (Preferred C 1-4 ) alkyl or C 1-6 (Preferred C 1-4 ) hydroxyalkyl),
[0076] Urea (-NH-C(=O)-N(R 13 )2(Two R 13 independently represent hydrogen atoms or C 1-6 (Preferred C 1-4 )alkyl)),
[0077] -COO(CH2)2NHCOOR 14 (where R 14 Represents C 1-4 alkyl) or
[0078] -COO(CH2)2-NH-C(=O)-N(R 15 )2(Two R 15 independently represent hydrogen atoms or C 1-6 (Preferred C 1-4 )alkyl), and
[0079] R 2 represents a hydrogen atom or a methyl group. )
[0080] (In formula (3), R 3 Represents C 1-4 Alkyl and R 4 represents a hydrogen atom or a methyl group. )
[0081] When SP 21 is the SP value of the second monomer unit (J / cm 3 ) 0.5 From the perspective of fixing performance, SP 21 It is preferably at least 21.00, or more preferably at least 25.00. The upper limit is not particularly limited, but is preferably not more than 40.00, or still more preferably not more than 30.00.
[0082] If the SP value of the second monomer unit is within this range, the cross-linking effect with the polyvalent metal element is enhanced, and hot offset resistance is improved.
[0083] The content of the first resin (crystalline resin) in the binder resin is preferably at least 30.0% by mass.
[0084] Within this range, both low temperature fixability and hot offset resistance can be achieved because a domain-matrix structure composed of a matrix containing the first resin and a domain containing the second resin is easily formed. The content is more preferably at least 50.0 mass %, or still more preferably at least 55.0 mass %.
[0085] The upper limit is not particularly limited, but is preferably not more than 97.0% by mass, or more preferably not more than 75.0% by mass.
[0086] The content of the second resin (non-crystalline resin) in the binder resin is preferably at least 3.0 mass %, or more preferably at least 25.0 mass %. The upper limit is preferably not more than 70.0 mass %, or more preferably not more than 50.0 mass %, or still more preferably not more than 40.0 mass %.
[0087] One feature is that the acid value of the second resin (non-crystalline resin) is 0.5 mg KOH / g to 40 mg KOH / g. Within this range, low temperature fixability and hot offset resistance are improved because the first resin and the polyvalent metal element are more likely to interact with each other, or in other words, because ionic crosslinking of the resin by the polyvalent metal element is more likely to occur, and the improvement effect of the dispersion of the domains of the second resin is more likely to be obtained.
[0088] If the acid value of the second resin is less than 0.5 mg KOH / g, these effects are not obtained. If the acid value of the second resin exceeds 40 mg KOH / g, the charge maintenance in a high humidity environment in particular may be reduced and fogging may occur because the hydrophobicity of the toner particle surface is reduced. A range of 1 mg KOH / g to 30 mg KOH / g is more preferred, 3 mg KOH / g to 25 mg KOH / g is still more preferred, and 6 mg KOH / g to 20 mg KOH / g is still more preferred.
[0089] Examples of the second resin include the following resins: single polymers of styrene and substituted styrenes, such as poly-p-chlorostyrene and polyvinyltoluene; styrene copolymers such as styrene-p-chlorostyrene copolymer, styrene-vinyltoluene copolymer, styrene-vinylnaphthalene copolymer, styrene-acrylate copolymer, styrene-methacrylate copolymer, styrene-α-chloromethyl methacrylate copolymer, styrene-acrylonitrile copolymer, styrene-vinyl methyl ether copolymer, styrene-vinyl ethyl ether copolymer, styrene-vinyl methyl ketone copolymer and styrene-acrylonitrile-indene copolymer; and polyvinyl chloride, phenolic resin, natural resin modified phenolic resin, natural resin modified maleic acid resin, acrylic resin, methacrylic resin, polyvinyl acetate, silicone resin, polyester resin, polyurethane resin, polyamide resin, furan resin, epoxy resin, xylene resin, polyvinyl butyral resin, terpene resin, coumarone-indene resin and petroleum-based resin.
[0090] Among them, from the viewpoint of charge-raising performance, the second resin is preferably at least one selected from the group consisting of vinyl resins (e.g., styrene copolymers), polyester resins, and hybrid resins containing vinyl resins connected to polyester resins. The connection here may refer to connection through a covalent bond. The second resin more preferably contains a polyester resin, and still more preferably is a polyester resin.
[0091] The second resin is described below using an example of a polyester resin.
[0092] The polyester resin is preferably a polycondensate of an alcohol component and a carboxylic acid component.
[0093] The acid value of the second resin can be controlled, for example, by changing the contents and kinds of the alcohol unit and the carboxylic acid unit in the non-crystalline resin.
[0094] The alcohol unit in the second resin is a structure obtained by polycondensation of a monomer as an alcohol component, or in other words, a monomer unit derived from an alcohol component. In addition, the carboxylic acid unit in the second resin is a structure obtained by polycondensation of a monomer as a carboxylic acid component, or in other words, a monomer unit derived from a carboxylic acid component.
[0095] From the viewpoint of charge-raising performance, the structure obtained by polycondensation of bisphenol A alkylene oxide adduct preferably constitutes at least 75 mol%, or more preferably at least 80 mol%, or still more preferably at least 90 mol% of the alcohol unit. An example of bisphenol A alkylene oxide adduct is a compound represented by the following formula (A):
[0096]
[0097] (In formula (A), each R is independently an ethylene group or a propylene group, x and y are each an integer of 0 or at least 0, and the average value of x+y is 0 to 10).
[0098] In view of the charge increasing performance, the bisphenol A alkylene oxide adduct is preferably a bisphenol A propylene oxide adduct and / or an ethylene oxide adduct, and more preferably a propylene oxide adduct. The average value of x+y is preferably 1 to 5, and more preferably 1.6 to 2.8.
[0099] The following polyol components can be used as other components other than the bisphenol A alkylene oxide adduct for forming the alcohol unit: ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, 1,4-butenediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,4,5-pentanetriol, glycerol, 2-methylpropylenetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, 1,3,5-trihydroxymethylbenzene.
[0100] The peak molecular weight Mp of the second resin is preferably 3,000 to 30,000, or more preferably 5,000 to 20,000, or still more preferably 10,000 to 15,000, from the viewpoint of low-temperature fixability and hot offset resistance.
[0101] The carboxylic acid unit preferably includes at least one selected from the group consisting of an aromatic dicarboxylic acid polycondensation structure, a saturated aliphatic dicarboxylic acid polycondensation structure, and an unsaturated dicarboxylic acid polycondensation structure.
[0102] Examples of the aromatic dicarboxylic acids include phthalic acid, isophthalic acid, and terephthalic acid, and anhydrides thereof.
[0103] From the viewpoint of charge-raising performance, alkyl dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, adipic acid, suberic acid, azelaic acid, and sebacic acid, and anhydrides thereof are desirable as the saturated aliphatic dicarboxylic acids.
[0104] For example, fumaric acid, maleic acid, citraconic acid, itaconic acid and C 6-18 Unsaturated dicarboxylic acids such as alkenyl-substituted succinic acid and their anhydrides are desirable as the unsaturated dicarboxylic acids. In particular, dodecenyl succinic acid is desirable. It is more desirable to combine at least two of the above-mentioned saturated aliphatic dicarboxylic acids and unsaturated dicarboxylic acids.
[0105] That is, it is preferred that the second resin is a polyester resin, and the polyester resin has a polycondensation structure of dodecenylsuccinic acid or its anhydride. In addition, the polyester resin preferably has a polycondensation structure of other carboxylic acid components other than the polycondensation structure of dodecenylsuccinic acid or its anhydride.
[0106] When the polyester resin has a polycondensation structure of dodecenylsuccinic acid or its anhydride, the toner has good hot offset resistance because the polyester resin interacts more easily with the polyvalent metal element and the metal ion crosslinking effect is increased.
[0107] The content of the polycondensation structure of dodecenylsuccinic acid or its anhydride in the carboxylic acid unit is preferably 10 mol % to 30 mol %, or more preferably 15 mol % to 20 mol %.
[0108] In view of charge-raising performance and hot offset resistance, the carboxylic acid unit preferably includes a polycondensation structure of an aromatic tricarboxylic acid or an aromatic tetracarboxylic acid.
[0109] Examples of the aromatic tricarboxylic acid include trimellitic acid or trimellitic anhydride.Examples of the aromatic tetracarboxylic acid include pyromellitic acid and pyromellitic anhydride.
[0110] The polycondensation structure of the aromatic carboxylic acid preferably constitutes 50 mol% to 80 mol%, or more preferably 55 mol% to 75 mol% of the carboxylic acid unit.
[0111] Increasing the content ratio of the aromatic carboxylic acid relative to the aliphatic dicarboxylic acid is expected to improve charge retention.
[0112] Examples of the aromatic carboxylic acid include the aforementioned aromatic dicarboxylic acids, aromatic tricarboxylic acids, and aromatic tetracarboxylic acids.
[0113] Other carboxylic acids used to form the carboxylic acid unit include 6-18 Alkyl-substituted succinic acid or its anhydride, and polycarboxylic acids such as 1,2,3,4-butanetetracarboxylic acid and benzophenonetetracarboxylic acid and their anhydrides.
[0114] The non-crystalline polyester resin may be produced using any conventionally used catalyst including metals such as tin, titanium, antimony, manganese, nickel, zinc, lead, iron, magnesium, calcium, and germanium, and compounds containing these metals.
[0115] Among them, tin compounds are expected to improve charging performance. Examples of tin compounds include organic tin compounds such as dibutyltin dichloride, dibutyltin oxide, and diphenyltin oxide, etc. The organic tin compound here is a compound having a Sn-C bond.
[0116] Inorganic tin compounds having no Sn-C bond can also be advantageously used. The inorganic tin compound here is a compound having no Sn-C bond.
[0117] Examples of the inorganic tin compound include unbranched alkyl tin carboxylates such as tin diacetate, tin dihexanoate, tin dioctoate and tin stearate, branched alkyl tin carboxylates such as tin dipivalate and tin di(2-ethylhexanoate), tin carboxylates such as tin oxalate, and dialkoxytin such as dioctyl tin and distearoxytin.
[0118] Among these tin compounds, tin alkylcarboxylates or tin dialkoxides are preferred, and tin dioctoate, tin di(2-ethylhexanoate), and tin stearate, which are tin alkylcarboxylates having a carboxyl residue in the molecule, are particularly desirable.
[0119] The dielectric constant of the second resin (non-crystalline resin) at 2kHz is preferably 2.0 pF / m to 3.0 pF / m. Within this range, when inorganic fine particles are added as external additives, the charge retention under high temperature and high humidity conditions is improved due to the improved charge transfer between the second resin and the inorganic fine particles. A range of 2.2 pF / m to 2.8 pF / m is more preferred. The dielectric constant of the second resin can be controlled by changing the monomer composition and the acid value.
[0120] The binder resin preferably contains a third resin. The third resin preferably contains a resin including a first resin (crystalline resin) connected to a second resin (non-crystalline resin), and more preferably a resin including a first resin connected to a second resin. When such a third resin is included, good charge rise performance, low temperature fixability, and heat offset resistance are obtained. The third resin, for example, preferably has a structure in which at least parts of the first resin and the second resin are connected together.
[0121] Methods of connecting the first resin and the second resin include a method of cross-linking by applying a radical initiator to a mixture obtained by melting or fusing the first resin and the second resin, and a method of cross-linking using a cross-linking agent having a functional group reactive with both the first resin and the second resin, and the like.
[0122] The radical initiator used in the method of cross-linking using a radical initiator is not particularly limited, and may be an inorganic peroxide, an organic peroxide, or an azo compound, etc. These radical reaction initiators may also be combined.
[0123] When both the first resin and the second resin have carbon-carbon unsaturated bonds, these bonds can be broken when the first resin and the second resin are cross-linked. When one or both of the first resin and the second resin do not have carbon-carbon unsaturated bonds, the two are cross-linked by extracting hydrogen atoms bonded to carbon atoms contained in the first resin and / or the second resin. In this case, the free radical initiator is more preferably an organic peroxide having a strong hydrogen abstraction ability.
[0124] There is no particular limitation on the cross-linking agent having a functional group reactive with both the first resin and the second resin, and known agents such as a cross-linking agent having an epoxy group, a cross-linking agent having an isocyanate group, a cross-linking agent having an oxazoline group, a cross-linking agent having a carbodiimide group, a cross-linking agent having a hydrazide group, or a cross-linking agent having an aziridine group, etc. may be used.
[0125] In the method of cross-linking using a cross-linking agent having a functional group reactive with both the first resin and the second resin, both the first and second resins must have a functional group reactive with the cross-linking agent.
[0126] A resin in which at least a part of the first resin and the second resin crosslinked by the above method are linked together (ie, a resin composition containing the first resin and the second resin, and a third resin obtained by crosslinking the first and second resins) can be used to manufacture a toner.
[0127] When the toner is produced by a melt-kneading method, toner particles including a resin including a first resin linked to a second resin can be produced by melt-kneading a raw material mixture containing the first and second resins in the presence of the above-mentioned radical initiator or crosslinking agent.
[0128] The content of the third resin in the binder resin is preferably 1.0% by mass to 20.0% by mass, or more preferably 5.0% by mass to 15.0% by mass.
[0129] For example, the third resin is preferably a resin obtained by adding a radical reaction initiator while melt-kneading a non-crystalline polyester resin having a carbon-carbon double bond (second resin) with the first resin to thereby perform a crosslinking reaction.
[0130] When the third resin is made using the first resin and the second resin, at least part of the first resin and the second resin are connected together to form the third resin. This produces a binder resin containing the first resin, the second resin and the third resin.
[0131] The binder resin containing the first resin, the second resin and the third resin can also be obtained by connecting at least part of the first resin and the second resin together. The binder resin can also be obtained by separately manufacturing the third resin and then mixing it with the first resin and the second resin.
[0132] The radical reaction initiator used for the cross-linking reaction is not particularly limited, and may be an inorganic peroxide, an organic peroxide, or an azo compound, etc. These radical reaction initiators may also be combined.
[0133] The inorganic peroxide is not particularly limited, and examples include hydrogen peroxide, ammonium peroxide, potassium peroxide, sodium peroxide, and the like.
[0134] There are no particular limitations on the organic peroxide, and examples include benzoyl peroxide, di-tert-butyl peroxide, tert-butylcumyl peroxide, dicumyl peroxide, α,α-di(tert-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, di-tert-hexyl peroxide, 2,5-dimethyl-2,5-di-t-butylperoxyhexine-3 , acetyl peroxide, isobutyryl peroxide, octanoyl peroxide, decanoyl peroxide, lauroyl peroxide, 3,3,5-trimethylhexanoyl peroxide, m-toluoyl peroxide, tert-butyl peroxyisobutyrate, tert-butyl peroxyneodecanoate, cumyl peroxyneodecanoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxylaurate, tert-butyl peroxybenzoate, tert-butyl peroxyisopropyl monocarbonate, and tert-butyl peroxyacetate, etc.
[0135] The azo compound or diazo compound is not particularly limited, and examples include 2,2'-azobis-(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2,'-azobis-4-methoxy-2,4-dimethylvaleronitrile, and azobisisobutyronitrile.
[0136] Among them, organic peroxides are desirable because they have high initiator efficiency and do not generate toxic byproducts such as cyanide compounds.
[0137] A reaction initiator having a high hydrogen abstraction ability is desirable because the cross-linking reaction can be efficiently carried out with a smaller amount of the initiator, and a free radical reaction initiator having a high hydrogen abstraction ability such as tert-butyl peroxyisopropyl monocarbonate, benzoyl peroxide, di-tert-butyl peroxide, tert-butylcumyl peroxide, dicumyl peroxide, α,α-di(tert-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane or di-tert-hexyl peroxide is even more desirable.
[0138] The amount of the radical reaction initiator used is not particularly limited, but is preferably 0.1 to 50 parts by mass, or more preferably 0.2 to 5 parts by mass, relative to 100 parts by mass of the binder resin to be crosslinked.
[0139] The mass ratio X / Y of the content X of the first resin to the content Y of the second resin in the binder resin is preferably 0.2 to 2.5, or more preferably 2.0 to 2.4 from the viewpoints of low temperature fixing property, hot offset resistance and charge maintenance property.
[0140] The number average diameter of the domains in cross-sectional observation of the toner is preferably 0.1 μm to 2.0 μm, or more preferably 0.5 μm to 1.5 μm, from the viewpoint of low-temperature fixability and hot offset resistance.
[0141] If the number average diameter of the domains is not more than 2.0 μm, fixing performance improves because the crystalline resin of the matrix and the non-crystalline resin of the domains are more easily melted when fixing the toner particles. In addition, hot offset is suppressed because the viscosity of the molten matrix is maintained at an appropriate level in a high temperature region.
[0142] If the number average diameter of the domains is at least 0.1 μm, low-temperature fixability improves because the sharp melting property of the crystalline resin can be appropriately obtained.
[0143] The number average diameter of the domains can be controlled by the monomer composition of the crystalline resin and the non-crystalline resin, the production conditions, and the like.
[0144] Polyvalent metal elements
[0145] The toner particles contain a polyvalent metal element. The polyvalent metal element is at least one selected from the group consisting of Mg, Ca, Al, Fe and Zn. When the polyvalent metal element is included, the polyvalent metal element orients itself to the polar portion of the first and second resins and can form a network crosslink that contributes to the toner's fixing performance. Thus, a toner having excellent low-temperature fixing performance and heat offset resistance can be obtained.
[0146] Preferably, the toner particles contain a polyvalent metal element in a non-phase separation state. The non-phase separation state is, for example, an invisible state. This means that, for example, a polyvalent metal having a particle size of no more than 100 nm is contained. In the observation method discussed below, if the particle size of the polyvalent metal cannot be observed, the particle size is judged to be no more than 100 nm.
[0147] If the polyvalent metal element does not include at least one selected from the group consisting of Mg, Ca, Al, Fe and Zn, or when a polyvalent metal element having a relatively high molecular weight such as Sr or Ba is selected, the amount of crosslinking points relative to the amount of the polyvalent metal element added is reduced, and the crosslinking forming effect is reduced. As a result, low-temperature fixing property, hot offset resistance and charge maintenance are reduced.
[0148] The compound containing a polyvalent metal element is preferably a non-magnetic compound. The toner is preferably a non-magnetic toner.
[0149] The total content of the polyvalent metal element in the toner is 0.0025 to 3.0000 parts by mass relative to 100 parts by mass of the binder resin. If the content ratio of the polyvalent metal element is within this range, crosslinking can occur appropriately between the first monomer unit and the polyvalent metal element, forming a crosslinking portion that improves low-temperature fixability and hot offset resistance.
[0150] If the content ratio of the polyvalent metal element is less than 0.0025 parts by mass, the crosslinking points between the polyvalent metal element and the polar parts of the first and second resins are reduced. Low temperature fixability and hot offset resistance are also reduced because the improvement effect of the dispersion type of the domains of the second resin in the domain-matrix structure is not obtained.
[0151] On the other hand, if the content ratio of the polyvalent metal element exceeds 3.0000 parts by mass, low-temperature fixability and charging performance are reduced because the crosslinking portion between the polar portion and the polyvalent metal element becomes excessive.
[0152] The content ratio of the polyvalent metal element is preferably 0.0025 to 0.0500 parts by mass, or more preferably 0.0150 to 0.0300 parts by mass, relative to 100 parts by mass of the binder resin.
[0153] Preferably, the content ratio of the polyvalent metal element in the toner and the content ratio of the first monomer unit in the first resin are in a relationship represented by the following formula (2):
[0154] (parts by mass of the polyvalent metal element relative to 100 parts by mass of the binder resin in the toner particles)×10000 / (ratio of content of the first monomer unit in the first resin)≥0.5 (parts by mass / % by mass)…(2)
[0155] If the above formula (2) is satisfied, it means that the ratio of the polyvalent metal element to the polar part is within a range in which the polyvalent metal element and the crystalline resin are easily interacted with each other. Within this range, excellent low-temperature fixability, hot offset resistance, and charge maintenance are obtained because the domains of the non-crystalline resin can be finely dispersed in the matrix of the crystalline resin to form a suitable domain-matrix structure. (Parts by mass of the polyvalent metal element relative to 100 parts by mass of the binder resin in the toner particles) × 10000 / (content ratio of the first monomer unit in the first resin) is more preferably 1.0 to 5.0.
[0156] Preferably, the toner particles contain a monovalent metal element, and the monovalent metal element is at least one selected from the group consisting of Na, Li and K. When the monovalent metal element is contained, the polar part in the binder resin can form a crosslink not only between the polar part and the polyvalent metal element, but also between the polar part and the monovalent metal element. This produces a toner having excellent low-temperature fixing ability, hot offset resistance and charging performance.
[0157] The content of the monovalent metal element is preferably 45% to 90% by mass based on the total content of the polyvalent metal element and the monovalent metal element. From the viewpoint of low temperature fixing property, hot offset resistance and charge maintenance, it is desirable that the content of the monovalent metal element is within this range.
[0158] The content of the monovalent metal element is more preferably 60% by mass to 80% by mass based on the total content of the polyvalent metal element and the monovalent metal element.
[0159] The complex elastic modulus of the toner at 65°C is preferably 1.00×10 7 Pa to 5.00×10 7 The complex elastic modulus of the toner at 85°C is preferably not more than 1.00×10 6 Pa.
[0160] If the complex elastic modulus at 65°C is 1.00×10 7 Pa to 5.00×10 7 Pa, crosslinks are favorably formed between the polar portion and at least one of the polyvalent metal element and the monovalent metal element, resulting in even more excellent low-temperature fixability and hot offset resistance.
[0161] If the complex elastic modulus at 85°C does not exceed 1.00×10 6 Pa, the crosslink formed between the polar portion and at least one of the polyvalent metal element and the monovalent metal element has an appropriate strength to be released when exceeding the melting point, resulting in more excellent low-temperature fixability.
[0162] The complex elastic modulus of the toner at 65°C is preferably 2.00×10 7 Pa to 4.50×10 7 Pa.
[0163] The complex elastic modulus of the toner at 85°C is preferably not more than 0.95×10 6 Pa. There is no particular lower limit, but it is preferred that the complex elastic modulus of the toner at 85°C is at least 0.10×10 6 Pa.
[0164] The complex elastic modulus can be controlled by controlling the monomer composition, molecular weight, production conditions, and the like of the binder resin.
[0165] The average circularity of the toner is preferably from 0.950 to 0.999, or more preferably from 0.960 to 0.990.
[0166] The first resin (crystalline resin) may further contain a third monomer unit different from the first monomer unit represented by the above formula (1) and the second monomer unit represented by the above formula (2) or (3).
[0167] The polymerizable monomer capable of forming the third monomer unit includes styrene and derivatives thereof such as styrene and o-methylstyrene, (meth)acrylates such as 2-ethylhexyl methacrylate, and (meth)acrylic acid.
[0168] The content ratio of the third monomer unit in the first resin is preferably 1.0% by mass to 30.0% by mass, or more preferably 5.0% by mass to 20.0% by mass.
[0169] Colorants
[0170] The toner may contain a colorant as required. Examples of the colorant are shown below.
[0171] Examples of black colorants include carbon black and colorants adjusted to black by using yellow colorants, magenta colorants and cyan colorants. Pigments can be used alone, and dyes and pigments can be used in combination as colorants. From the viewpoint of the image quality of full-color images, it is preferred to use dyes and pigments in combination.
[0172] Examples of pigments for magenta toners include CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75 7:1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, and 282; CI Pigment Violet 19; and CI Vat Red 1, 2, 10, 13, 15, 23, 29, and 35.
[0173] Examples of dyes for magenta toners include CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, and 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; oil-soluble dyes such as CI Disperse Violet 1, and CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, and 40; and basic dyes such as CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, and 28.
[0174] Examples of the pigment for cyan toner include CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, and 17; CI Vat Blue 6; and CI Acid Blue 45, and copper phthalocyanine pigments having 1 to 5 phthalimidomethyl substituents in the phthalocyanine skeleton.
[0175] Examples of the dye for cyan toner include CI Solvent Blue 70.
[0176] Examples of the pigment for yellow toner include CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181 and 185; and CI Vat Yellow 1, 3 and 20.
[0177] Examples of the dye for yellow toner include CI Solvent Yellow 162.
[0178] The content of the colorant is preferably 0.1 to 30.0 parts by mass relative to 100 parts by mass of the binder resin.
[0179] Release agent
[0180] The toner particles may include wax as a release agent. Examples of such wax are shown below.
[0181] Hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline waxes, paraffin waxes, and Fischer-Tropsch waxes; oxides of hydrocarbon waxes such as oxidized polyethylene waxes or block copolymers thereof; waxes based on fatty acid esters such as carnauba wax; and partially or fully deoxygenated fatty acid esters such as deoxygenated carnauba wax. Saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassidic acid, eleostearic acid, and valinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohols, behenyl alcohol, carnaub alcohol, wax alcohol, and myricol; polyols such as sorbitol; fatty acids such as palmitic acid, stearic acid, behenyl alcohol, and montanic acid and fatty acids such as stearyl alcohol, aralkyl alcohols, behenyl alcohol, carnaub alcohol, wax alcohol, and myricol; esters of alcohols such as linoleyl alcohol, wax alcohol, and myricyl alcohol; fatty acid amides such as linoleamide, oleamide, and lauramide; saturated fatty acid bisamides such as methylene bisstearamide, ethylene bisdecylamide, ethylene bislauramide, and hexamethylene bisstearamide; unsaturated fatty acid amides such as ethylene bisoleamide, hexamethylene bisoleamide, N,N'-dioleyl adipic acid amide, and N,N'-dioleyl sebacic acidamide; aromatic bisamides such as m-xylene bisstearamide and N,N'-distearyl isophthalic acid amide; amide; aliphatic metal salts such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate (commonly referred to as metal soaps); waxes obtained by grafting vinyl monomers such as styrene and acrylic acid to aliphatic hydrocarbon waxes; partial esterification products of fatty acids and polyols such as behenic acid monoglyceride; and methyl ester compounds having a hydroxyl group obtained by hydrogenating vegetable oils and fats.
[0182] The content of the wax is preferably 2.0 to 30.0 parts by mass relative to 100 parts by mass of the binder resin.
[0183] Charge control agent
[0184] The toner may optionally contain a charge control agent.
[0185] As the charge control agent, known ones can be used, but in particular, a colorless metal compound of an aromatic carboxylic acid which can accelerate the charging speed of the toner and stably maintain a constant charge amount is preferred.
[0186] Examples of negative charge control agents include metal compounds of salicylic acid, metal compounds of naphthoic acid, metal compounds of dicarboxylic acids, polymer compounds having sulfonic acid or carboxylic acid in the side chain, polymer compounds having sulfonate or sulfonate compounds in the side chain, polymer compounds having carboxylate or carboxylate compounds in the side chain, boron compounds, urea compounds, silicon compounds, and calixarene.
[0187] The charge control agent may be added to the toner particles internally or externally. The amount of the charge control agent is preferably 0.2 parts by mass to 10 parts by mass relative to 100 parts by mass of the binder resin.
[0188] Inorganic fine particles
[0189] The toner may contain inorganic fine particles as necessary.
[0190] The inorganic fine particles may be added internally to the toner particles, or may be mixed with the toner particles as an external additive. Examples of the inorganic fine particles include fine particles such as silica fine particles, titanium oxide fine particles, aluminum oxide fine particles, or fine particles of their composite oxides. Among the inorganic fine particles, silica fine particles and titanium oxide fine particles are preferred from the viewpoint of improving fluidity and charging uniformity.
[0191] The inorganic fine particles are preferably hydrophobized by a hydrophobizing agent such as a silane compound, silicone oil, or a mixture thereof.
[0192] Silica fine particles produced by any method can be advantageously used, including, for example, by a wet method such as a precipitation method or a sol-gel method in which silica is obtained by neutralizing sodium silicate, or a dry method such as a Verneuil method or an arc method in which silica is obtained in a vapor phase. Among them, silica fine particles produced by a sol-gel method or a Verneuil method are desirable because the number average diameter of primary particles is more easily controlled within a desired range.
[0193] From the viewpoint of improving fluidity, the inorganic fine particles as the external additive preferably have a particle size of 50 m 2 / g to 400m 2 From the viewpoint of improving durability stability, the inorganic fine particles as external additives preferably have a specific surface area of 10 m 2 / g to 50m 2 In order to ensure both improvement in fluidity and durable stability, inorganic fine particles having a specific surface area within these ranges may be used in combination.
[0194] The amount of the external additive is preferably 0.1 parts by mass to 10.0 parts by mass relative to 100 parts by mass of the toner particles. A known mixer such as a Henschel mixer can be used to mix the toner particles with the external additive.
[0195] Developer
[0196] The toner may be used as a one-component developer, but is preferably mixed with a magnetic carrier and used as a two-component developer in order to further improve dot reproducibility and supply stable images over a long period of time.
[0197] In other words, a two-component developer containing a toner and a magnetic carrier, wherein the toner is the toner of the present disclosure, is preferred.
[0198] Examples of magnetic carriers include known materials such as iron oxide; metal particles such as iron, lithium, calcium, magnesium, nickel, copper, zinc, cobalt, manganese, chromium, and rare earth metals, alloy particles thereof, and oxide particles thereof; magnetic bodies such as ferrite; a magnetic body-dispersed resin carrier (so-called resin carrier) containing a magnetic body and a binder resin for holding the magnetic body in a dispersed state, etc.
[0199] When the toner is used as a two-component developer by mixing with a magnetic carrier, the mixing ratio of the magnetic carrier at this time is preferably 2% by mass to 15% by mass and more preferably 4% by mass to 13% by mass as the toner concentration in the two-component developer.
[0200] In the gel permeation chromatography measurement of the tetrahydrofuran soluble matter of the toner, the weight average molecular weight is taken as Mw(A), and the number average molecular weight is taken as Mn(A).
[0201] Mw(A) is preferably 25,000 to 60,000, or more preferably 32,000 to 48,000.
[0202] Mw(A) / Mn(A) is preferably 5-10, or more preferably 7-8.
[0203] Mn(A) is preferably 3,000 to 8,500, or more preferably 4,000 to 6,000.
[0204] Mw(A) can be controlled by controlling the monomer composition and molecular weight of the binder resin and the production conditions.
[0205] Mw(A) / Mn(A) can be controlled by controlling the monomer composition and molecular weight of the binder resin and the production conditions.
[0206] Within these ranges, low temperature fixability and hot offset resistance improve.The peak molecular weight in a molecular weight distribution curve obtained by GPC measurement of a THF soluble of toner particles is preferably 7,000 to 11,000, or more preferably 8,200 to 10,500.
[0207] If the peak molecular weight is within this range, low temperature fixability and hot offset resistance are improved.
[0208] When the molecular weight distribution curve has a plurality of peaks, the peak molecular weight in the molecular weight distribution curve obtained by GPC measurement of a THF soluble matter of toner particles is the molecular weight of the highest peak.
[0209] Method for producing toner
[0210] The method for producing the toner of the present disclosure is not particularly limited, and a known method such as a pulverization method, a suspension polymerization method, a dissolution suspension method, an emulsion aggregation method, or a dispersion polymerization method can be used.
[0211] The toner herein is preferably produced by the method described below. That is, the toner is preferably produced by an emulsion aggregation method. In the case of the emulsion aggregation method, it is easy to form a desired domain-matrix structure in the toner.
[0212] A method for producing a toner, the method comprising:
[0213] a step of preparing a dispersion of fine resin particles containing a binder resin;
[0214] a step of adding a coagulant to the resin fine particle dispersion to form aggregated particles; and
[0215] a step of heating and fusing the aggregated particles to obtain a dispersion liquid containing toner particles, wherein the binder resin comprises a first resin and a second resin,
[0216] The first resin is a crystalline resin,
[0217] The second resin is a non-crystalline resin,
[0218] The first resin has a first monomer unit represented by formula (1),
[0219] The content ratio of the first monomer unit in the first resin is 30.0 mass % to 99.9 mass %,
[0220] The acid value of the first resin is 0.1 mg KOH / g to 30 mg KOH / g,
[0221] The acid value of the second resin is 0.5 mg KOH / g to 40 mg KOH / g,
[0222] A domain-matrix structure formed by a matrix containing the first resin and a domain containing the second resin appears in cross-sectional observation of the toner,
[0223] The toner particles contain a polyvalent metal element,
[0224] The polyvalent metal element is at least one metal element selected from the group consisting of Mg, Ca, Al, Fe and Zn, and
[0225] The total content of the polyvalent metal elements is 0.0025 parts by mass to 3.0000 parts by mass relative to 100 parts by mass of the binder resin.
[0226] In the method, the coagulant preferably includes a metal salt of at least one metal element selected from the group consisting of Mg, Ca, Al, Fe and Zn.
[0227] Emulsion aggregation method
[0228] In the emulsion aggregation method, an aqueous dispersion of fine particles sufficiently smaller than a desired particle size and composed of constituent materials of toner particles is prepared in advance, the fine particles are aggregated to the particle size of toner particles in an aqueous medium, and a resin is fused by heating or the like to produce toner particles.
[0229] That is, in the emulsion aggregation method, colorant particles are produced by the following: a dispersion step of preparing a fine particle dispersion solution composed of the constituent materials of the colorant particles, an aggregation step of aggregating the fine particles composed of the constituent materials of the colorant particles, and controlling the particle size until the particle size of the colorant particles is obtained, a fusion step of fusing the resin contained in the obtained aggregated particles, a subsequent cooling step, a metal removal step of filtering out the obtained colorant and removing excess polyvalent metal ions, a washing step of filtering and washing with ion exchange water or the like, and a step of removing moisture from the washed colorant particles and drying.
[0230] Method for preparing resin fine particle dispersion (dispersion step)
[0231] The resin fine particle dispersion can be prepared by known methods, but is not limited to these methods. Examples of known methods include emulsion polymerization, self-emulsification, phase inversion emulsification in which an aqueous medium is added to a resin solution obtained by dissolving the resin in an organic solvent to emulsify the resin, and forced emulsification in which the resin is forcibly emulsified by high-temperature treatment in an aqueous medium without using an organic solvent.
[0232] Specifically, the binder resin is dissolved in an organic solvent that can dissolve the resin, and a surfactant or an alkaline compound is added. At this time, the binder resin is a crystalline resin with a melting point, and the resin can be dissolved by melting to a temperature higher than the melting point. Subsequently, an aqueous medium is slowly added while stirring with a homogenizer or the like to precipitate fine resin particles. Thereafter, an aqueous solution in which the fine resin particles are dispersed is prepared by removing the solvent by heating or decompression. Any organic solvent that can dissolve the resin can be used as an organic solvent for dissolving the resin, but from the viewpoint of suppressing the generation of coarse powder, an organic solvent that forms a homogeneous phase with water, such as toluene, is preferred.
[0233] The surfactant used in emulsification is not particularly limited, and examples thereof include anionic surfactants such as sulfates, sulfonates, carboxylates, phosphates, and soaps, etc.; cationic surfactants such as amine salts, and quaternary ammonium salts, etc.; and nonionic surfactants such as polyethylene glycol, alkylphenol ethylene oxide adducts, and polyols, etc. A single surfactant or a combination of two or more thereof may be used.
[0234] Examples of the basic compound used in the dispersing step include inorganic bases such as sodium hydroxide, potassium hydroxide, etc., and organic bases such as ammonia, triethylamine, trimethylamine, dimethylaminoethanol, and diethylaminoethanol, etc. A single basic compound or a combination of two or more thereof may be used.
[0235] The 50% particle size (D50) based on volume distribution of the fine particles of the binder resin in the aqueous solution in which the fine particles of the resin are dispersed is preferably 0.05 μm to 1.0 μm, and more preferably 0.05 μm to 0.4 μm. By adjusting the 50% particle size (D50) based on volume distribution to the above range, it is easy to obtain toner particles having a volume average particle size of 3 μm to 10 μm suitable for toner particles.
[0236] A dynamic light scattering type particle size distribution analyzer NANOTRAC UPA-EX150 (manufactured by Nikkiso Co., Ltd.) was used for the measurement of the 50% particle diameter (D50) based on volume distribution.
[0237] Colorant fine particle dispersion
[0238] The colorant fine particle dispersion liquid used as necessary can be prepared by known methods listed below, but is not limited to these methods.
[0239] The colorant fine particle dispersion can be prepared by mixing the colorant, aqueous medium and dispersant using a mixer such as a known stirrer, emulsifier, and disperser. The dispersant used here may be a known one such as a surfactant and a polymer dispersant.
[0240] Although any surfactant and polymer dispersant may be removed in the cleaning step described below, surfactants are preferred from the viewpoint of cleaning efficiency.
[0241] Examples of the surfactant include anionic surfactants such as sulfates, sulfonates, carboxylates, phosphates, and soaps; cationic surfactants such as amine salts, and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycol, alkylphenol ethylene oxide adducts, and polyols.
[0242] Among them, nonionic surfactants and anionic surfactants are preferred. In addition, nonionic surfactants and anionic surfactants can be used together. A single surfactant or a combination of two or more thereof can be used. The concentration of the surfactant in the aqueous medium is preferably 0.5% by mass to 5% by mass.
[0243] The amount of the colorant fine particles in the colorant fine particle dispersion liquid is not particularly limited, but is preferably 1% by mass to 30% by mass relative to the total mass of the colorant fine particle dispersion liquid.
[0244] In addition, from the viewpoint of the dispersibility of the colorant in the toner finally obtained, the dispersed particle size of the colorant fine particles in the aqueous solution in which the colorant fine particles are dispersed is preferably such that the 50% particle size (D50) based on the volume distribution is 0.5 μm or less. Further, for the same reason, the 90% particle size (D90) based on the volume distribution is preferably 2 μm or less. The dispersed particle size of the colorant particles dispersed in the aqueous medium is measured by a dynamic light scattering type particle size distribution analyzer (NANOTRAC UPA-EX150: manufactured by Nikkiso Co., Ltd.)
[0245] Known mixers such as stirrers, emulsifiers, and dispersers for dispersing colorants in aqueous media include ultrasonic homogenizers, jet mills, pressure homogenizers, gel mills, ball mills, sand mills, and paint shakers. These can be used alone or in combination.
[0246] Release agent (aliphatic hydrocarbon compound) fine particle dispersion
[0247] The release agent fine particle dispersion may be used as required. The release agent fine particle dispersion may be prepared by the following known methods, but is not limited to these methods.
[0248] The release agent fine particle dispersion can be prepared by adding the release agent to an aqueous medium including a surfactant, heating to a temperature equal to or higher than the melting point of the release agent, dispersing into a granular state with a homogenizer having a strong shearing ability (e.g., "CLEARMIX W MOTION" manufactured by MTechnique Co., Ltd.) or a pressurized discharge type disperser (e.g., "GAULIN HOMOGENIZER" manufactured by Gaulin Co., Ltd.), and then cooling to below the melting point.
[0249] The dispersed particle size of the release agent fine particle dispersion in the release agent dispersed aqueous solution is preferably such that the 50% particle size (D50) based on volume distribution is 0.03 to 1.0 μm, and more preferably 0.1 to 0.5 μm. In addition, coarse particles of 1 μm or more are preferably absent.
[0250] When the dispersed particle size of the release agent fine particle dispersion is within the above range, the release agent can be finely dispersed to be present in the toner, the bleeding effect during fixing can be maximized, and good separation can be obtained. The dispersed particle size of the release agent fine particle dispersion obtained by dispersing in an aqueous medium can be measured by a dynamic light scattering type particle size distribution analyzer (NANOTRAC UPA-EX 150: manufactured by Nikkiso Co., Ltd.).
[0251] Mixing Steps
[0252] In the mixing step, a mixed liquid is prepared by mixing the resin fine particle dispersion with at least one of the release agent fine particle dispersion and the colorant fine particle dispersion as necessary. The mixing can be performed using a known mixing device such as a homogenizer and a mixer.
[0253] Aggregate particle formation step (aggregation step)
[0254] In the aggregation step, the fine particles contained in the mixed solution prepared in the mixing step are aggregated to form aggregates having a target particle size. At this time, a coagulant is added and mixed, and as required, at least one of heating and mechanical power is appropriately added to form aggregates in which the resin fine particles and, as required, at least one of the release agent fine particles and the colorant fine particles are aggregated.
[0255] The coagulant preferably includes a coagulant of metal ions of a polyvalent metal as a polyvalent metal element, and the polyvalent metal is at least one selected from the group consisting of Mg, Ca, Al, Fe, and Zn.
[0256] The coagulant including the metal ions of the polyvalent metal has high aggregation power, and the purpose can be achieved by adding it in a small amount. Such a coagulant can ionically neutralize the ionic surfactant contained in the resin fine particle dispersion, the release agent fine particle dispersion, and the colorant fine particle dispersion. Therefore, the binder resin fine particles, the release agent fine particles, and the colorant fine particles are aggregated by salting out and ionic crosslinking effects. In addition, the coagulant including the metal ions of the polyvalent metal can form crosslinks with the first resin. Therefore, the crosslinking points of the polyvalent metal and the polar part of the toner particles can be formed in the mesh of the entire toner particles while forming the domain matrix structure. Thus, excellent charge maintenance can be displayed without damaging the low-temperature fixability.
[0257] Examples of coagulants containing metal ions of polyvalent metals include metal salts of polyvalent metal elements or polymers of metal salts. Specific examples include divalent inorganic metal salts such as calcium chloride, calcium nitrate, magnesium chloride, magnesium sulfate and zinc chloride. Other examples include trivalent metal salts such as iron (III) chloride, iron (III) sulfate, aluminum sulfate and aluminum chloride. Other examples include, but are not limited to, inorganic metal salt polymers such as ferric polysulfate, polyaluminum chloride, polyaluminum hydroxide and polycalcium sulfate. A single one of these or a combination of at least two can be used.
[0258] Among these coagulants, magnesium-based coagulants are preferred because of their strong crosslinking effect with the binder resin and their dispersion effect in the second resin.
[0259] The coagulant may be added in the form of a dry powder or an aqueous solution obtained by dissolving in an aqueous medium, but in order to produce uniform aggregation, the coagulant is preferably added in the form of an aqueous solution.
[0260] In addition, it is preferred to add and mix the coagulant at a temperature equal to or lower than the glass transition temperature or melting point of the resin contained in the mixed solution. By mixing under such temperature conditions, aggregation is performed relatively uniformly. The mixing of the coagulant into the mixed solution can be performed using known mixing devices such as homogenizers and mixers. The aggregation step is a step of forming aggregates of the size of the toner particles in an aqueous medium. The volume average particle size of the aggregates produced in the aggregation step is preferably 3 μm to 10 μm. The volume average particle size can be measured by a particle size distribution analyzer (Coulter Multisizer III: manufactured by Beckman Coulter, Inc.) by the Coulter method.
[0261] Step of obtaining a dispersion containing toner particles (melting step)
[0262] In the melting step, an aggregation-stopping agent is added to the dispersion containing aggregates obtained in the aggregation step while stirring similarly to the aggregation step. The aggregation-stopping agent can be exemplified by a chelating agent that stabilizes aggregated particles by partially dissociating ionic crosslinks between the acidic polar groups of the surfactant and the metal ions as the coagulant and forming a coordinate bond with the metal ions. By adding the aggregation-stopping agent, the crosslinking points between the polar part of the toner particles and the polyvalent metal can be controlled to an optimal amount, so that an excellent effect of hot offset resistance and excellent charge maintenance can be exhibited without impairing excellent low-temperature fixability.
[0263] After the dispersion state of the aggregated particles in the dispersion liquid is stabilized by the action of the aggregation stopper, the aggregated particles are fused by heating to a temperature equal to or higher than the glass transition temperature or melting point of the binder resin.
[0264] There is no particular limitation on the chelating agent as long as it is a known water-soluble chelating agent. Specific examples include hydroxycarboxylic acids such as tartaric acid, citric acid and gluconic acid, and sodium salts thereof; iminodiacid (IDA), nitrilotriacetic acid (NTA), and ethylenediaminetetraacetic acid (EDTA), and sodium salts of these acids.
[0265] The chelating agent coordinates to the metal ions of the coagulant present in the dispersion of aggregated particles, so that the environment in the dispersion can be changed from an electrostatically unstable state in which aggregation can easily occur to an electrostatically stable state in which further aggregation is not likely to occur. Therefore, further aggregation of aggregated particles in the dispersion can be suppressed and the aggregated particles can be stabilized.
[0266] The chelating agent is preferably an organic metal salt having a trivalent or higher carboxylic acid, since even a small amount of such a chelating agent can be effective and can obtain toner particles having a clear particle size distribution.
[0267] Furthermore, from the viewpoint of achieving both stabilization from the aggregated state and cleaning efficiency, the amount of the chelating agent added is preferably 1 to 30 parts by mass and more preferably 2.5 to 15 parts by mass relative to 100 parts by mass of the binder resin. The 50% particle size (D50) based on volume of the toner particles is preferably 3 μm to 10 μm.
[0268] Cooling Steps
[0269] If necessary, in the cooling step, the temperature of the dispersion containing the toner particles obtained in the melting step may be lowered to a temperature lower than at least one of the crystallization temperature and the glass transition temperature of the binder resin. By cooling to a temperature lower than at least one of the crystallization temperature and the glass transition temperature, the generation of coarse particles can be prevented. The specific cooling rate may be 0.1°C / min to 50°C / min.
[0270] Metal Removal Step
[0271] In the toner manufacturing method, it is desirable to include a metal removal step, in which a chelate compound having a chelate function for metal ions is added to a dispersion containing toner particles to remove at least part of a polyvalent metal element and thereby adjust the content of the polyvalent metal element. The concentration distribution of the polyvalent metal element on the surface of the toner particles can be controlled by means of the metal removal step. Specifically, the concentration of the polyvalent metal element in the surface layer of the toner particles can be made lower than the concentration of the polyvalent metal element inside the toner particles, resulting in excellent low-temperature fixing property, heat offset resistance, and charge maintenance.
[0272] The chelate compound is not particularly limited as long as it is a known water-soluble chelate, and the above-mentioned chelates can be used. Since the metal removal ability of the water-soluble chelate is extremely sensitive to temperature, the metal removal step is preferably performed at a temperature of 40°C to 60°C, or more preferably at about 50°C.
[0273] Cleaning steps
[0274] As required, impurities in the toner particles can be removed by repeatedly washing and filtering the toner particles obtained in the cooling step in the washing step. Specifically, it is preferred to wash the toner particles by using an aqueous solution containing a chelating agent such as ethylenediaminetetraacetic acid (EDTA) and its Na salt, and further washing with pure water. By repeatedly washing with pure water and drying, metal salts and surfactants in the toner particles can be removed. From the viewpoint of production efficiency, the number of filtrations is preferably 3 to 20 times and more preferably 3 to 10 times.
[0275] Drying Steps
[0276] In the drying step, the toner particles obtained in the above steps are dried as necessary.
[0277] External Addition Steps
[0278] The obtained toner particles can also be used as a toner as they are.
[0279] In the external addition step, inorganic particles are externally added as needed to treat the toner particles obtained in the drying step. Specifically, inorganic fine particles such as silica or resin particles such as vinyl resins, polyester resins, or silicone resins are preferably added by applying shear force in a dry state.
[0280] For example, a mixture of toner particles and inorganic fine particles together with other external additives can be mixed by a mixing apparatus such as a double cone mixer, V-type mixer, drum mixer, super mixer, Henschel mixer, Nauta mixer, Mechano Hybrid (Nippon Coke & Engineering Co., Ltd.), or Nobilta (Hosokawa Micron Corporation).
[0281] Methods of measuring various physical properties of toner particles and raw materials will be described below.
[0282] Method for measuring the amount of metal elements in toner particles
[0283] The amount of the metal element in the toner particles is measured using a multi-element simultaneous ICP emission spectrophotometer Vista-PRO (manufactured by Hitachi High-Tech Science Co., Ltd.).
[0284] Sample: 50mg
[0285] Solvent: 6 mL of nitric acid
[0286] The above materials were weighed and subjected to decomposition treatment using a microwave sample pretreatment device ETHOS UP (manufactured by Milestone General Co., Ltd.).
[0287] Temperature: Increase from 20°C to 230°C and maintain at 230°C for 30 minutes.
[0288] The decomposed liquid was passed through filter paper (5C), transferred to a 50 mL volumetric flask, and fixed to 50 mL with ultrapure water. The amount of multivalent metal elements (e.g., Mg, Ca, Al, Fe, and Zn) and monovalent metal elements (Na, Li, and K) in the toner particles can be quantified by measuring the aqueous solution in the volumetric flask under the following conditions using a multi-element simultaneous ICP emission spectrophotometer Vista-PRO. For the quantification of the amount, a calibration curve was prepared using a standard sample of the element to be quantified, and calculations were performed based on the calibration curve.
[0289] Conditions: RF power 1.20kW,
[0290] Ar gas: plasma flow 15.0L / min,
[0291] Auxiliary flow: 1.50L / min,
[0292] MFC: 1.50L / min,
[0293] Nevizer Flow: 0.90L / min,
[0294] Pump speed: 15rpm,
[0295] Measurement repetition: 3 times,
[0296] Measuring time: 1.0s
[0297] (Measurement of a case where a toner to which inorganic fine particles including at least one metal element selected from the group consisting of Mg, Ca, Al, Fe, and Zn are externally added)
[0298] When measuring the amount of metal elements in toner particles of a toner to which inorganic fine particles including at least one metal element selected from the group consisting of Mg, Ca, Al, Fe, and Zn are externally added, the measurement is performed after the inorganic fine particles have been separated from the toner in order to prevent the amount of metal elements derived from the inorganic fine particles other than the metal element forming a crosslink with the polar part from being calculated. Specifically, the method is as follows.
[0299] Separation of inorganic fine particles from toner
[0300] The inorganic fine particles can also be separated from the toner by the following method.
[0301] 200g sucrose (Kishida Chemical) is added to 100mL ion exchange water, and dissolved in a hot water bath to prepare a concentrated sucrose solution. 31g concentrated sucrose solution and 6mL Contaminon N (10% by mass pH 7 neutral detergent aqueous solution for washing precision instruments, which comprises nonionic surfactant, anionic surfactant and organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) are added to a centrifuge tube to prepare a dispersion. 1g toner is added to the dispersion, and toner lumps are broken with a spatula or the like.
[0302] The centrifuge tube was shaken in an oscillator (KM Shaker (model: V.SX) IWAKI CO., LTD.) at a speed of 350 reciprocating times per minute for 20 minutes. After shaking, the solution was transferred to a glass tube for a swing rotor (50 mL) and centrifuged in a centrifuge at 3500 rpm for 30 minutes. After centrifugation, the toner particles were present in the uppermost layer in the glass tube, while the inorganic fine particles were present in the aqueous solution at the lower layer. The toner particles at the uppermost layer were collected.
[0303] The aqueous solution in the lower layer is collected and centrifuged to separate sucrose from the inorganic fine particles, and the inorganic fine particles are collected. Centrifugation is repeated as needed, and once separation is sufficient, the dispersion is dried and the inorganic fine particles are collected.
[0304] When a plurality of types of inorganic fine particles have been added, these inorganic fine particles may be selected by centrifugation or the like.
[0305] When the toner particles contain a magnetic body, further centrifugation is performed under the same conditions. The toner particles are separated in the upper layer and the magnetic body in the lower layer.
[0306] Confirmation of the non-phase separation state of multivalent metal elements
[0307] The toner cross section is observed by the following method, and if no polyvalent metal is observed, this means that the toner particles contain the polyvalent metal element in a non-phase-separated state having a particle diameter of not more than 100 nm.
[0308] In order to determine the presence or absence of multivalent elements not observed in the toner cross section, element mapping was performed using an X-ray analyzer (SEM-EDX). The measuring unit was an EDAX energy dispersive X-ray analyzer. The mapped elements were magnesium, aluminum, calcium, iron, and zinc.
[0309] The mapping conditions are as follows.
[0310] Accelerating voltage: 200 kV
[0311] Electron beam irradiation size: 1.5nm
[0312] Live time limit: 600 seconds
[0313] Dead time: 20 to 30
[0314] Mapping resolution: 256×256
[0315] When there is a peak in the spectrum of any of the above elements (average of 10 nm squares) and the particle diameter in cross-sectional observation of the toner is not more than 100 nm, the toner particles are judged to contain the polyvalent metal element in a non-phase-separated state.
[0316] Dielectric Constant Measurement Method
[0317] The complex dielectric constant was measured at a frequency of 2 kHz using a 284A precision LCR meter (Hewlett Packard) after calibration at frequencies of 1 kHz and 1 MHz. A pressure of 39200 kPa (400 kg / cm 2) for 5 minutes to form a disk-shaped measurement sample having a diameter of 25 mm and a thickness of 1 mm or less (preferably 0.5 to 0.9 mm). The measurement sample is mounted on an ARES (Rheometric Scientific FE) equipped with a dielectric constant measurement fixture (electrode) having a diameter of 25 mm, and measured at a frequency of 2 kHz under a load of 0.49 N (50 g) in an atmosphere of 25°C.
[0318] Method for measuring the content ratio of each monomer unit in the first resin
[0319] Pass under the following conditions 1 H-NMR measures the content ratio of each monomer unit in the first resin.
[0320] Measuring unit: FT NMR unit JNM-EX400 (JEOL Ltd.)
[0321] Measuring frequency: 400MHz
[0322] Pulse condition: 5.0μs
[0323] Frequency range: 10500Hz
[0324] Number of points: 64
[0325] Measuring temperature: 30℃
[0326] Sample: 50 mg of a measurement sample was placed in a sample tube with an inner diameter of 5 mm, deuterated chloroform (CDCl3) was added as a solvent, and it was dissolved in a constant temperature bath at 40°C to prepare.
[0327] In the obtained 1 In the H-NMR chart, among the peaks attributable to the constituent elements of the first monomer unit, a peak independent of peaks attributable to constituent elements of monomer units from other sources is selected, and the integrated value S1 of the peak is calculated.
[0328] Similarly, a peak independent of peaks of constituent elements attributed to monomer units of other origins is selected from the peaks of constituent elements attributed to the second monomer unit, and the integrated value S2 of the peak is calculated.
[0329] When the first resin contains the third monomer unit, a peak independent of peaks of constituent elements attributed to monomer units of other origins is selected from peaks of constituent elements attributed to the third monomer unit, and an integrated value S3 of the peak is calculated.
[0330] The content of the first monomer unit is determined as follows using the integrated values S1, S2, and S3: n1, n2, and n3 are the numbers of hydrogen atoms of the constituent element to which the observed peaks for each segment are attributed.
[0331] Content of the first monomer unit (mol%) =
[0332] {(S1 / n1) / ((S1 / n1)+(S2 / n2)+(S3 / n3))}×100.
[0333] The second and third monomer units are similarly determined as shown below.
[0334] Content of the second monomer unit (mol%) =
[0335] {(S2 / n2) / ((S1 / n1)+(S2 / n2)+(S3 / n3))}×100.
[0336] Content of the third monomer unit (mol%) =
[0337] {(S3 / n3) / ((S1 / n1)+(S2 / n2)+(S3 / n3))}×100.
[0338] When a polymerizable monomer containing no hydrogen atom in the constituent elements other than the vinyl group is used as the first resin, 13 C-NMR 13 C is used as the measurement core in single pulse mode and is measured with 1 The ratio was calculated in the same manner as in H-NMR.
[0339] When a toner is manufactured by a suspension polymerization method, since the peaks of a release agent and other resins overlap, an independent peak may not be observed. Therefore, the ratio of monomer units derived from each polymerizable monomer in the first resin may not be calculated. In this case, the first resin ' can be manufactured and analyzed by performing similar suspension polymerization without using a release agent or other resins.
[0340] SP value calculation method
[0341] Such as SP 21 The equivalent SP value is determined as follows according to the calculation method proposed by Fedors.
[0342] The evaporation energy (Δei) (cal / mol) and molar volume (Δvi) (cm2) of the atoms or atomic groups in the molecular structure of each polymerizable monomer were determined from the table described in "Polym. Eng. Sci., 14 (2), 147-154 (1974)". 3 / mol), and (4.184×∑Δei / ∑Δvi) 0.5 Considered as SP value (J / cm 3 ) 0.5 .
[0343] For atoms or atomic groups in the molecular structure of the same polymerizable monomer having double bonds that are broken by polymerization, SP is calculated by a similar method. 21 .
[0344] Melting point measurement method
[0345] For example, the melting point of the resin is measured using DSC Q1000 (TA Instruments) under the following conditions.
[0346] Heating rate: 10℃ / min
[0347] Measurement start temperature: 20°C
[0348] Measurement end temperature: 180℃
[0349] The melting points of indium and zinc are used for temperature correction of the detection portion of the device, and the heat of fusion of indium is used for correction of the calorific value.
[0350] Specifically, 5 mg of the sample was accurately weighed into an aluminum pan and subjected to differential scanning calorimetry. An empty silver pan was used as a reference.
[0351] The peak temperature of the maximum endothermic peak during the first temperature increase was regarded as the melting point.
[0352] When there are multiple peaks, the maximum endothermic peak is the peak at which the amount of endothermic heat is the largest.
[0353] Method for measuring the peak molecular weight and weight average molecular weight of THF soluble matter of resin by GPC
[0354] The peak molecular weight and weight average molecular weight (Mw) of THF-soluble matter of a resin such as the first resin or the second resin are measured by gel permeation chromatography (GPC) as follows.
[0355] First, the sample was dissolved in tetrahydrofuran (THF) at room temperature over a 24-hour period. The resulting solution was filtered through a solvent-resistant membrane filter (Maishori Disk, Tosoh Corp.) having a pore size of 0.2 μm to obtain a sample solution. The concentration of THF-solubles in the sample solution was adjusted to about 0.8% by mass. The sample solution was used for measurement under the following conditions.
[0356] System: HLC8120 GPC (Detector: RI) (Tosoh Corp.)
[0357] Chromatographic columns: Shodex KF-801, 802, 803, 804, 805, 806, 807 (7 in total) (Showa Denko)
[0358] Eluent: Tetrahydrofuran (THF)
[0359] Flow rate: 1.0mL / min
[0360] Oven temperature: 40.0℃
[0361] Sample injection volume: 0.10mL
[0362] A molecular weight calibration curve prepared using standard polystyrene resin (product name: TSK standard polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500, Tosoh Corp.) was used to calculate the molecular weight of the sample.
[0363] Method for measuring molecular weight of THF-soluble matter of toner
[0364] 0.5 mg of the toner to be tested is dissolved in 1 g of THF and dispersed by ultrasonication, and then the concentration is adjusted to 0.5%, and the dissolved components are measured by GPC.
[0365] HLC-8120GPC and SC-8020 (Tosoh) were used as GPC units, two TSK gels and Super HM-H columns (Tosoh, 6.0 mm ID×15 cm) were used as columns, and THF was used as an eluent.
[0366] As for the test conditions, the test was performed using a refractive index (RI) detector at a sample concentration of 0.5%, a flow rate of 0.6 ml / min, a sample injection amount of 10 μl, and a measurement temperature of 40°C.
[0367] A calibration curve was also prepared using Tosoh TSK standard polystyrenes A-500, F-1, F-10, F-80, F-380, A-2500, F-4, F-40, F-128 and F-700 (10 samples in total).
[0368] Method for measuring the softening point of resin
[0369] The softening point of the resin is measured using a constant load extrusion capillary rheometer (Shimadzu Corporation, CFT-500D Flowtester flow characteristics evaluation device) according to the attached manual. Using this device, the temperature of the measurement sample contained in the barrel is raised to melt the sample, and a certain load is applied to the measurement sample from above with a piston, and the molten measurement sample is extruded through a die at the bottom of the barrel, and then a flow curve can be obtained, which shows the relationship between the temperature and the amount of descent of the piston during this process.
[0370] In the present invention, the "melting temperature of the 1 / 2 method" as described in the manual attached to the CFT-500D Flowtester flow property evaluation apparatus is taken as the softening point.
[0371] The melting temperature of the 1 / 2 method is calculated as follows.
[0372] Half of the difference between the piston descent at the end of outflow (outflow end point, given as "Smax") and the piston descent at the start of outflow (lowest point, given as "Smin") is determined and given as X (X = (Smax-Smin) / 2). The temperature in the flow curve when the piston descent is the sum of X and Smin is the melting temperature of the 1 / 2 method.
[0373] For the measurement sample, about 1.0 g of the resin is compression-molded with a tablet molding press (eg, NPa Systems Co., Ltd., NT-100H) at about 10 MPa for about 60 seconds at 25° C. to obtain a cylindrical sample with a diameter of about 8 mm.
[0374] The specific operation of the measurement is carried out according to the device manual.
[0375] The measurement conditions of CFT-500D are as follows.
[0376] Test mode: Heating method
[0377] Starting temperature: 50℃
[0378] Reaching temperature: 200℃
[0379] Measuring interval: 1.0℃
[0380] Heating rate: 4.0℃ / min
[0381] Piston cross-sectional area: 1.000cm 2
[0382] Test load (piston load): 10.0kgf (0.9807MPa)
[0383] Warm-up time: 300 seconds
[0384] Die hole diameter: 1.0mm
[0385] Mold length: 1.0mm
[0386] Measurement of glass transition temperature (Tg) of resin
[0387] The glass transition temperature (Tg) was measured using a differential scanning calorimeter (TA Instruments, Q2000) according to ASTM D3418-82.
[0388] The melting points of indium and zinc are used for temperature correction of the detection part of the device, and the heat of fusion of indium is used for calibrating the calorimetric value.
[0389] Specifically, 3 mg of a sample was accurately weighed, placed in an aluminum pan, and measured using an empty aluminum pan as a reference under the following conditions.
[0390] Heating rate: 10℃ / min
[0391] Measurement start temperature: 30°C
[0392] Measurement end temperature: 180℃
[0393] During the measurement, the temperature was first raised to 180°C and held for 10 minutes, then lowered to 30°C at a rate of 10°C / min, and then raised again. During this second temperature increase, the specific heat change was obtained in the temperature range of 30°C to 100°C. The glass transition temperature (Tg) is the intersection of the differential thermal curve and the midline between the baselines before and after the specific heat change occurs.
[0394] Method for measuring acid value (Av) of polymer A and non-crystalline resin other than polymer A
[0395] The acid value is the number of milligrams of potassium hydroxide required to neutralize acid components such as free fatty acids and resin acids contained in 1 g of a sample. The acid value is measured in accordance with JIS K 0070-1992.
[0396] (1) Reagents
[0397] A total of 1.0 g of phenolphthalein was dissolved in 90 mL of ethanol (95% by volume), and ion-exchanged water was added to adjust the volume to 100 mL to obtain a phenolphthalein solution.
[0398] The special grade potassium hydroxide amounting to 7g is dissolved in the water of 5mL, and ethanol (95 volume %) is added to be constant to 1L. The solution is placed in an alkali-resistant container and left to stand for 3 days, while preventing contact with carbon dioxide gas etc., and filtered thereafter to obtain potassium hydroxide solution. The potassium hydroxide solution obtained is stored in an alkali-resistant container. The 0.1mol / L hydrochloric acid amounting to 25mL is placed in a conical flask, a few drops of phenolphthalein solution are added thereto, and titration is performed with potassium hydroxide solution, and the factor of potassium hydroxide solution is determined by the amount of potassium hydroxide solution required for neutralization. Use the hydrochloric acid of 0.1mol / L prepared according to JIS K 8001-1998.
[0399] (2) Operation
[0400] (A) Main test
[0401] 2.0 g of the crushed sample was accurately weighed into a 200 mL conical flask, 100 mL of a mixed solution of toluene / ethanol (2:1) was added, and dissolved for 5 hours. Thereafter, a few drops of phenolphthalein solution were added as an indicator, and titrated using potassium hydroxide solution. The endpoint of the titration was assumed to be when the light pink color of the indicator lasted for about 30 seconds.
[0402] (B) Blank test
[0403] Titration was performed in the same manner as above except that no sample was used (ie, only a mixed solution of toluene / ethanol (2:1) was used).
[0404] (3) The acid value is calculated by substituting the obtained result into the following formula.
[0405] A=[(CB)×f×5.61] / S
[0406] Here, A: acid value (mg KOH / g), B: amount of potassium hydroxide solution added in the blank test (mL), C: amount of potassium hydroxide solution added in the main test (mL), f: factor of potassium hydroxide solution, and S: mass of sample (g).
[0407] Method for measuring weight average particle size (D4) of toner
[0408] The weight average particle size (D4) of the toner (or toner particles) is calculated as follows. A precision particle size distribution measuring device (registered trademark, "Coulter Counter Multisizer 3", manufactured by Beckman Coulter, Inc.) based on the pore resistance method and comprising a nozzle with a diameter of 100 μm is used as a measuring device. The dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.) provided with the device is used to set the measurement conditions and analyze the measurement data. The measurement is performed with 25,000 effective measurement channels.
[0409] A solution prepared by dissolving special grade sodium chloride in ion exchange water to a concentration of about 1% by mass, such as "ISOTON II" manufactured by Beckman Coulter, Inc., can be used as the aqueous electrolyte solution used for measurement.
[0410] Before performing measurement and analysis, set the dedicated software in the following manner.
[0411] In the "Change Standard Observation Method (SOM)" interface of the dedicated software, the total count in the control mode was set to 50,000 particles, the number of measurements was set to 1, and the value obtained using "Standard Particles 10.0 μm" (manufactured by Beckman Coulter, Inc.) was set as the Kd value. By pressing the "Threshold / Noise Level Measurement" button, the threshold and noise level were automatically set. In addition, the current was set to 1600 μA, the gain was set to 2, the electrolyte was set to ISOTON II, and the check of "Flushing of the mouth tube after measurement" was entered.
[0412] In the "Pulse to Particle Size Conversion Settings" interface of the dedicated software, the element interval is set to logarithmic particle size, the particle diameter bin is set to 256 particle diameter bins, and the particle size range is set to 2 μm to 60 μm.
[0413] The specific measurement method is as follows.
[0414] (1) Place approximately 200 mL of electrolyte aqueous solution in a 250 mL round-bottom beaker dedicated to Multisizer 3, place the beaker on the sample stage, and stir counterclockwise at 24 rpm with a stirring rod. Remove dirt and bubbles in the nozzle using the "Nozzle Rinse" function of the dedicated software.
[0415] (2) About 30 mL of an aqueous electrolyte solution was placed in a 100 mL glass flat-bottom beaker. Then, about 0.3 mL of a dilution prepared by diluting "CONTAMINON N" (a 10% by mass aqueous solution of a neutral detergent at pH 7 for cleaning precision measuring instruments, composed of a nonionic surfactant, an anionic surfactant and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) with three times the mass of deionized water was added thereto as a dispersant.
[0416] (3) An ultrasonic disperser "Ultrasonic Dispersion System Tetora 150" (manufactured by Nikkaki Bios Co., Ltd.) with a power output of 120 W was prepared in which two oscillators with an oscillation frequency of 50 kHz were assembled with a phase shift of 180°. A total of 3.3 L of ion-exchanged water was placed in the tank of the ultrasonic disperser, and about 2 mL of CONTAMINON N was added to the water tank.
[0417] (4) The beaker in (2) is placed in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is started. Then, the height position of the beaker is adjusted to maximize the resonance state of the liquid surface of the aqueous electrolyte solution in the beaker.
[0418] (5) In a state where the electrolyte aqueous solution in the beaker of (4) above is irradiated with ultrasonic waves, a total of 10 mg of toner is gradually added to the electrolyte aqueous solution and dispersed. Then, the ultrasonic dispersion treatment is further continued for 60 seconds. During the ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to 10° C. to 40° C.
[0419] (6) Using a pipette, the aqueous electrolyte solution in which the toner is dispersed in (5) is dropped into the round bottom beaker in (1) set on the sample stage, and the measurement concentration is adjusted to about 5%. Then, measurement is performed until the number of particles measured reaches 50,000.
[0420] (7) Analyze the measurement data using the dedicated software provided by the equipment and calculate the weight-average particle size (D4). When the dedicated software is set to Graph / Volume %, the "Average Diameter" on the "Analysis / Volume Statistics (Arithmetic Mean)" interface is the weight-average particle size (D4).
[0421] Method for measuring average circularity of toner
[0422] The average circularity of the toner is measured by a flow-type particle image analyzer "FPIA-3000" (manufactured by Sysmex Corporation) under the measurement and analysis conditions at the time of calibration.
[0423] The measurement principle of the flow particle image analyzer "FPIA-3000" (manufactured by Sysmex Corporation) is to capture the image of flowing particles as a static image and perform image analysis. The sample added to the sample chamber is sent to the planar sheath flow cell by the sample suction syringe.
[0424] The sample sent into the planar sheath flow cell is clamped by the sheath liquid to form a planar flow. The sample passing through the planar sheath flow cell is irradiated with a flash lamp at intervals of 1 / 60 seconds, and the image of the flowing particles can be captured as a static image. In addition, since the flow is planar, the captured image is focused. The particle image is captured by a CCD camera, and the captured image is image processed at an image processing resolution of 512×512 pixels (0.37×0.37μm per pixel), the contour of each particle image is extracted, and the projection area S and perimeter L of the particle image are calculated.
[0425] Then, the circle equivalent diameter and circularity are determined using the area S and the circumference L. The circle equivalent diameter is the diameter of a circle having the same area as the projected area of the particle image, and the circularity C is determined as the value obtained by dividing the circumference of the circle determined by the circle equivalent diameter by the circumference of the particle projected image. The circularity is calculated by the following formula.
[0426] Circularity C = 2 × (π × S)1 / 2 / L
[0427] When the projected image is circular, the circularity is 1.000, and as the unevenness on the periphery of the particle image increases, the circularity value decreases. After calculating the circularity of each particle, the range of circularity from 0.200 to 1.000 is divided by 800, the arithmetic mean of the obtained circularity is calculated, and this value is defined as the average circularity.
[0428] The specific measurement method is as follows.
[0429] First, 20 mL of ion exchange water from which solid impurities etc. had been removed in advance was placed in a glass container. About 0.2 mL of a dilution prepared by diluting "CONTAMINON N" (a 10% by mass aqueous solution of a neutral detergent at pH 7 for cleaning precision measuring instruments, composed of a nonionic surfactant, an anionic surfactant and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) with three times the mass of ion exchange water was added thereto.
[0430] Further, about 0.02g of the measurement sample was added, and an ultrasonic disperser was used to perform dispersion treatment for 2 minutes to obtain a dispersion liquid for measurement. At this time, the dispersion liquid was appropriately cooled to a temperature of 10°C to 40°C. As an ultrasonic disperser, a desktop ultrasonic cleaner disperser ("VS-150" (manufactured by VELVO-CLEAR Co.) with an oscillation frequency of 50kHz and an electric power output of 150W was used, a predetermined amount of ion exchanged water was placed in a water tank, and about 2mL of CONTAMINON N was added to the water tank.
[0431] For measurement, a flow type particle image analyzer equipped with a standard objective lens (×10) was used, and a particle sheath "PSE-900A" (manufactured by Sysmex Corporation) was used as a sheath liquid. The dispersion prepared according to the procedure was introduced into the flow type particle image analyzer, and 3,000 toner particles were measured in the total count mode in the HPF measurement mode.
[0432] Then, the binarization threshold value at the time of particle analysis is set to 85%, the particle size to be analyzed is set to a circle-equivalent diameter of 1.98 μm to 39.96 μm, and the average circularity of the toner is obtained.
[0433] In the measurement, automatic focusing is performed before the start of measurement using standard latex particles (for example, "RESEARCH AND TESTparticles Latex Microsphere Suspensions 5200A", manufactured by Duke Scientific Inc., which are diluted with ion exchange water). Thereafter, focusing is preferably performed every 2 hours after the start of measurement.
[0434] Crystalline resin fine particles, non-crystalline resin fine particles, aliphatic hydrocarbon compound fine particles and colorant fine particles Method for measuring the 50% particle size (D50) based on volume of particles
[0435] Dynamic light scattering type particle size distribution meter NANOTRAC UPA-EX150 (manufactured by Nikkiso Co., Ltd.) is used to measure the 50% particle diameter (D50) based on volume distribution of crystalline resin fine particles, non-crystalline resin fine particles, aliphatic hydrocarbon compound fine particles and colorant fine particles. Specifically, the measurement is performed according to the following procedure.
[0436] In order to prevent aggregation of the measurement sample, the dispersion liquid in which the measurement sample is dispersed is introduced into an aqueous solution containing FAMILYFRESH (manufactured by Kao Corporation) and stirred. After stirring, the measurement sample is injected into the above device, measurement is performed twice and the average value is determined.
[0437] As measurement conditions, the measurement time is 30 seconds, the sample particle refractive index is 1.49, the dispersion medium is water, and the dispersion medium refractive index is 1.33.
[0438] The volume particle size distribution of the measurement sample is determined, and the particle diameter where the cumulative volume from the smaller particle diameter side in the cumulative volume distribution of the measurement result is 50% is taken as the 50% particle diameter (D50) based on the volume distribution of each particle.
[0439] Method for measuring complex elastic modulus of toner
[0440] A rotating plate type rheometer "ARES" (manufactured by TA INSTRUMENTS) was used as a measuring apparatus.
[0441] A sample obtained by pressure-molding the toner into a disk having a diameter of 25 mm and a thickness of 2.0±0.3 mm with a tablet molding machine under an environment of 25° C. is used as a measurement sample.
[0442] The sample is mounted on parallel plates, the temperature is raised from room temperature (25°C) to 110°C within 15 minutes to adjust the shape of the sample, and then cooled to the measurement start temperature of viscoelasticity. Then the measurement is started and the complex viscosity is measured. At this time, the measurement sample is set so that the initial normal force becomes 0. In addition, as described below, in subsequent measurements, the influence of the normal force can be offset by performing automatic tensile adjustment (Auto Tension Adjustment ON).
[0443] The measurement was performed under the following conditions.
[0444] (1) Use a parallel plate with a diameter of 25 mm
[0445] (2) The frequency is set to 6.28 rad / sec (1.0 Hz).
[0446] (3) The initial value of applied strain (Strain) was set to 1.0%.
[0447] (4) The temperature was measured at a temperature increase rate of 2.0°C / min between 40°C and 100°C. The following setting conditions of the automatic adjustment mode were used in the measurement. The measurement was performed in the automatic strain adjustment mode (Auto Strain).
[0448] (5) The maximum applied strain is set to 40.0%.
[0449] (6) The maximum allowable torque is set to 150.0 g·cm, and the minimum allowable torque is set to 0.2 g·cm.
[0450] (7) The strain adjustment is set to 20.0% of the current strain. During the measurement, the automatic tension adjustment mode (AutoTension) is used.
[0451] (8) The automatic stretching direction is set to compression.
[0452] (9) The initial static force was set to 10.0 g and the automatic stretch sensitivity was set to 40.0 g.
[0453] (10) As the operation mode of automatic stretching, the sample modulus is 1.0×10 3 Pa or above.
[0454] Method for observing toner cross section and method for analyzing matrix and domain
[0455] First prepare the slices as a reference sample for abundance.
[0456] First, the first resin (crystalline resin) is fully dispersed in a visible light curable resin (Aronix LCR series D800) and cured by exposure to short wavelength light. The resulting cured resin is cut with an ultrathin slicer equipped with a diamond knife to prepare a 250 nm sample slice. A sample of the second resin (non-crystalline resin) is prepared in the same manner.
[0457] The first resin and the second resin were mixed at a ratio of 0 / 100, 30 / 70, 70 / 30 and 0 / 100, and melt-kneaded to prepare a kneaded mixture. They were similarly dispersed in a visible light curable resin and cut to prepare a sample slice.
[0458] Next, these reference samples were observed in cross section by TEM-EDX using a transmission electron microscope (JEOL Ltd., JEM-2800 electron microscope), and element mapping was performed by EDX. The mapped elements were carbon, oxygen, and nitrogen.
[0459] The mapping conditions are as follows.
[0460] Accelerating voltage: 200 kV
[0461] Electron beam exposure size: 1.5nm
[0462] Live time limit: 600 seconds
[0463] Dead time: 20 to 30
[0464] Mapping resolution: 256×256
[0465] Based on the spectral intensity of each element (average of 10 nm square area), (oxygen element intensity / carbon element intensity) and (nitrogen element intensity / carbon element intensity) were calculated, and a calibration curve of the mass ratio of the first and second resins was prepared. When the monomer unit of the first resin contained nitrogen, the subsequent test was performed using the (nitrogen element intensity / carbon element intensity) calibration curve.
[0466] The toner samples were then analyzed.
[0467] First, the toner is fully dispersed in a visible light curable resin (Aronix LCR Series D800) and cured by exposure to short wavelength light. The resulting cured resin is cut with an ultrathin slicer equipped with a diamond knife to prepare a sample slice of 250nm. Then a transmission electron microscope (JEOL Ltd., JEM-2800 electron microscope) is used to observe the cut sample by TEM-EDX. The cross-sectional image of the toner particles is obtained and element mapping is performed by EDX. The mapped elements are carbon, oxygen and nitrogen.
[0468] The toner cross section for observation is selected as follows. First, the cross-sectional area of the toner is determined from the cross-sectional image, and the diameter of a circle having the same area as the cross-sectional area (equivalent circle diameter) is determined. Observation is limited to toner cross-sectional images in which the absolute value of the difference between the equivalent circle diameter and the weight-average particle size (D4) is within 1.0 μm.
[0469] For the domain confirmed in the observed image, (oxygen element intensity / carbon element intensity) and / or (nitrogen element intensity / carbon element intensity) are calculated based on the spectral intensity of each element (average of 10 nm squares), and the ratio of the first resin to the second resin is calculated based on comparison with the calibration curve. A domain in which the ratio of the second resin is 80% or more is considered to be a domain in the present disclosure.
[0470] The domain confirmed in the observed image was specified and binarized to determine the particle size of the domain present in the toner cross section. The particle size was taken as the domain diameter. It was measured at 10 points in each toner, and the calculated average value of the domains of the 10 toners was taken as the number average diameter. Image Pro PLUS (Nippon Roper KK) was used for binarization.
[0471] Method for separating materials in toner
[0472] Each material contained in the toner can be separated from the toner by utilizing the difference in solubility of each material in the solvent.
[0473] First separation: The toner is dissolved in methyl ethyl ketone (MEK) at 23° C., and the soluble matter (second resin) is separated from the insoluble matter (first resin, releasing agent, colorant, inorganic fine particles, etc.).
[0474] Second separation: The insoluble matter (first resin, releasing agent, colorant, inorganic fine particles, etc.) obtained in the first separation is dissolved in 100°C MEK, and the soluble matter (first resin, releasing agent) is separated from the insoluble matter (colorant, inorganic fine particles, etc.).
[0475] Third separation: The soluble matter (first resin, release agent) obtained in the second separation was dissolved in chloroform at 23° C. and separated into a soluble matter (first resin) and an insoluble matter (release agent).
[0476] Including the third resin
[0477] First separation: The toner is dissolved in methyl ethyl ketone (MEK) at 23° C., and solubles (second resin, third resin) are separated from insolubles (first resin, release agent, colorant, inorganic fine particles, etc.).
[0478] Second separation: The soluble matter (second resin, third resin) obtained in the first separation was dissolved in toluene at 23° C. and separated into a soluble matter (third resin) and an insoluble matter (second resin).
[0479] Third separation: The insoluble matter (first resin, release agent, colorant, inorganic fine particles, etc.) obtained in the first separation was dissolved in 100°C MEK and separated into soluble matter (first resin, release agent) and insoluble matter (colorant, inorganic fine particles, etc.).
[0480] Fourth separation: The soluble matter (first resin, release agent) obtained in the third separation was dissolved in chloroform at 23° C. and separated into a soluble matter (first resin) and an insoluble matter (release agent).
[0481] Measurement of Contents of First Resin and Second Resin in Binder Resin in Toner
[0482] The masses of the soluble matter and the insoluble matter obtained in the above separation step are measured to calculate the contents of the first resin and the second resin in the binder resin in the toner.
[0483] Example
[0484] The present invention is illustrated using the following examples. However, these are by no means limiting the present invention in any way. Unless otherwise stated, the parts in the following formulations are based on mass.
[0485] Production Example of Crystalline Resin C1
[0486]
[0487]
[0488] These materials were placed in a nitrogen atmosphere in a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube. As the mixture was heated to 70°C and the polymerization reaction was carried out for 12 hours, the inside of the reaction vessel was stirred at 200 rpm to obtain a solution of a polymer of the monomer composition dissolved in toluene. Thereafter, the solution was cooled to 25°C and then added to 1000.0 parts of methanol under stirring to precipitate methanol insolubles. The resulting methanol insolubles were filtered out, washed with methanol, and vacuum dried at 40°C for 24 hours to obtain crystalline resin C1. The weight average molecular weight of crystalline resin C1 is 68400, the melting point is 62°C, and the acid value is 10 mg KOH / g.
[0489] In NMR analysis, the crystalline resin C1 contained 28.9 mol% of monomer units derived from behenyl acrylate, 53.8 mol% of monomer units derived from methacrylonitrile, and 17.3 mol% of monomer units derived from styrene. The content ratio of the first monomer unit was 67.0 mass%.
[0490] The SP value of the monomer unit derived from the second polymerizable monomer is 29.13 (J / cm 3 ) 0.5 .
[0491] Production Example of Crystalline Resin C2
[0492] 470 parts of toluene were placed in an autoclave, replaced with nitrogen, and the temperature was raised to 105° C. in a sealed state while stirring. While the internal temperature of the autoclave was controlled at 105° C., a mixture of 500 parts of behenyl acrylate (C22), 250 parts of styrene, 250 parts of acrylonitrile, 20 parts of methacrylic acid, 5 parts of alkyl allyl sulfosuccinic acid sodium salt, 19 parts of 2-isocyanatoethyl acrylate, 3.7 parts of tert-butyl peroxy-2-ethylhexanoate and 240 parts of toluene was dropped and polymerized over 2 hours.
[0493] The same temperature was maintained for another 4 hours to complete the reaction, after which 16 parts of di-n-butylamine and 5 parts of a bismuth catalyst (Nitto Kasei Co., Ltd., Neostann U-600) were added, and the mixture was reacted at 90°C for 6 hours. The solvent was then removed at 100°C to obtain a crystalline resin C2. The crystalline resin C2 had a weight average molecular weight of 100,000, a melting point of 46°C, and an acid value of 10 mg KOH / g. The content ratio of the first monomer unit was 49.0% by mass.
[0494] The SP value of the monomer unit derived from acrylonitrile is 22.75 (J / cm 3 ) 0.5 .
[0495] Production Example of Crystalline Resin C3
[0496] 138 parts of xylene were placed in an autoclave, replaced with nitrogen, and the temperature was raised to 170° C. in a sealed state while stirring. While the internal temperature of the autoclave was controlled at 170° C., a mixed solution of 200 parts of behenyl acrylate (C22), 150 parts of styrene, 300 parts of acrylonitrile, 600 parts of vinyl acetate, 1.5 parts of di-tert-butyl peroxide and 100 parts of xylene was dropped and polymerized over 3 hours.
[0497] After the dropwise addition, the drip line was cleaned with 12 parts of xylene. The polymerization was then completed by maintaining at the same temperature for 4 hours. The solvent was removed at 100° C. under a reduced pressure of 0.5 to 2.5 kPa for 3 hours to obtain a crystalline resin C3.
[0498] The weight average molecular weight of the crystalline resin C3 was 45,000, the melting point was 60° C., the acid value was 10 mg KOH / g, and the content ratio of the first monomer unit was 23.5% by mass.
[0499] The SP value of the monomer unit derived from vinyl acetate is 18.31 (J / cm 3 ) 0.5 .
[0500] Production of Crystalline Resin C4
[0501] Dodecanediol: 34.5 parts (0.29 mol; relative to the total molar number of the polyol: 100.0 mol%)
[0502] Sebacic acid: 65.5 parts (0.28 mol; relative to the total molar number of the polycarboxylic acid: 100.0 mol%)
[0503] These materials were weighed into a reaction tank equipped with a cooling tube, a stirrer, a nitrogen introduction tube and a thermocouple. The flask was then purged with nitrogen, the temperature was gradually increased while stirring, and the mixture was reacted at 140° C. for 3 hours while stirring.
[0504] ·2-Ethylhexanoate Tin: 0.5 parts
[0505] Then, the material was added, the pressure inside the reaction container was reduced to 8.3 kPa, and the reaction mixture was reacted for 4 hours while maintaining the temperature at 200° C., after which the reaction container was gradually opened to return the pressure to normal pressure and obtain crystalline resin C4. The weight average molecular weight of crystalline resin C4 was 30,000, the melting point was 50° C., and the acid value was 10 mg KOH / g. The content ratio of the first monomer unit was 0% by mass.
[0506] Production Example of Crystalline Resin C5
[0507] 138 parts of xylene were placed in an autoclave, which was then purged with nitrogen, and thereafter the temperature was raised to 170° C. in a sealed state while stirring. While the internal temperature of the autoclave was controlled at 170° C., 450 parts of behenyl acrylate (C22), 150 parts of styrene, 150 parts of acrylonitrile, 1.5 parts of di-tert-butyl peroxide, and 100 parts of xylene were dropped and polymerized over 3 hours.
[0508] After the dropping, the drip irrigation tube was washed with 12 parts of xylene. The polymerization was then completed by maintaining at the same temperature for 4 hours. The solvent was removed at 100° C. under a reduced pressure of 0.5 to 2.5 kPa for 3 hours to obtain a crystalline resin C5.
[0509] The weight average molecular weight of the crystalline resin C5 was 14,000, the melting point was 60° C., the acid value was 0 mg KOH / g, and the content ratio of the first monomer unit was 60.0% by mass.
[0510] The SP value of the monomer unit derived from acrylonitrile is 22.75 (J / cm 3 ) 0.5 .
[0511] Production Example of Crystalline Resin C6
[0512] Crystalline resin C6 was obtained according to the production example of crystalline resin C3 except that the amount of behenyl acrylate (C22) was changed to 500 parts.
[0513] The weight average molecular weight of the crystalline resin C6 was 46,000, the melting point was 55° C., the acid value was 8 mg KOH / g, and the content ratio of the first monomer unit was 32.3% by mass.
[0514] Production Example of Crystalline Resin C7
[0515] Crystalline resin C7 was obtained according to the production example of crystalline resin C3 except that 200 parts of behenyl acrylate (C22) was changed to 500 parts of stearyl acrylate (C18).
[0516] The weight average molecular weight of the crystalline resin C7 was 38,000, the melting point was 50° C., the acid value was 3 mg KOH / g, and the content ratio of the first monomer unit was 32.3% by mass.
[0517] Production Example of Crystalline Resin C8
[0518] Crystalline resin C8 was obtained according to the production example of crystalline resin C3 except that the amount of behenyl acrylate (C22) was changed to 700 parts.
[0519] The weight average molecular weight of the crystalline resin C8 was 28,000, the melting point was 65° C., the acid value was 30 mg KOH / g, and the content ratio of the first monomer unit was 40.0% by mass.
[0520] Production Example of Non-Crystalline Resin A1
[0521] Polyoxypropylene (2.2)-2,2-bis(4-hydroxypropyl)propane: 73.4 parts (0.186 mol; relative to the total molar number of the polyol: 100.0 mol%)
[0522] Terephthalic acid: 11.6 parts (0.070 mol; 45.0 mol% relative to the total moles of polycarboxylic acid)
[0523] Adipic acid: 6.8 parts (0.047 mol; 30.0 mol% relative to the total moles of polycarboxylic acid)
[0524] · Tin di(2-ethylhexanoate): 0.5 parts
[0525] These materials were weighed into a reaction tank equipped with a cooling tube, a stirrer, a nitrogen introduction tube and a thermocouple. The inside of the flask was purged with nitrogen, the temperature was gradually increased while stirring, and the mixture was reacted while stirring at 200° C. for 2 hours.
[0526] The pressure in the reaction tank was then reduced to 8.3 kPa and maintained for 1 hour, after which the temperature was reduced to 180° C. and the pressure was returned to atmospheric pressure (first reaction step).
[0527] Trimellitic anhydride: 8.2 parts (0.039 mol; 25.0 mol% relative to the total moles of polycarboxylic acid)
[0528] Tert-butylcatechol (polymerization inhibitor): 0.1 part
[0529] Then, the above materials were added, the pressure in the reaction tank was reduced to 8.3 kPa, and the temperature was maintained at 160° C. while the reaction mixture was reacted for 15 hours. The temperature was lowered to stop the reaction (second reaction step) and obtain a non-crystalline resin A1. The obtained non-crystalline resin A1 had a peak molecular weight Mp of 11000, a glass transition temperature Tg of 58° C., and an acid value of 20 mg KOH / g.
[0530] Production Examples of Non-Crystalline Resins A2 and A4 to A9
[0531] Amorphous resins A2 and A4 to A9 were obtained by performing the same reaction as in the manufacturing example of the amorphous resin A1, except that the alcohol component or the carboxylic acid component and the molar ratio were changed as shown in Table 1-1. The mass parts of the raw materials were adjusted so that the total molar number of the alcohol component and the carboxylic acid component was the same as in the manufacturing example of the amorphous resin A1. The physical properties of the obtained amorphous resins are shown in Tables 1-1 and 1-2.
[0532] Production Example of Non-Crystalline Resin A3
[0533]
[0534] These materials were weighed into a reaction tank equipped with a cooling tube, a stirrer, a nitrogen introduction tube and a thermocouple. The inside of the flask was purged with nitrogen, the temperature was gradually increased while stirring, and the mixture was reacted while stirring at 200° C. for 5 hours to obtain non-crystalline resin A3.
[0535] The peak molecular weight of the obtained non-crystalline resin A3 obtained by GPC was 4700. The glass transition temperature Tg was 56° C., and the acid value was 7 mg KOH / g.
[0536] Production Example of Amorphous Resins A10 and A11
[0537] Amorphous resins A10 and A11 were obtained by performing the same reaction as in the manufacturing example of the amorphous resin A3, except that the alcohol component or the carboxylic acid component and the molar ratio were changed as shown in Tables 1-1 and 1-2. The mass parts of the raw materials were adjusted so that the total molar number of the alcohol component and the carboxylic acid component was the same as in the manufacturing example of the amorphous resin A3. The physical properties are shown in Tables 1-1 and 1-2.
[0538] Production Example of Non-Crystalline Resin A12
[0539] 50 parts of bisphenol A propylene oxide 2 mole adduct, 50 parts of bisphenol A ethylene oxide 2 mole adduct, 10 parts of fumaric acid, 65 parts of terephthalic acid, 10 parts of acrylic acid and 15 parts of tin (II) dioctoate were placed in a four-necked flask equipped with a thermometer, a stirrer, a condenser and a nitrogen inlet tube, and polymerized at 230° C. for 4.5 hours in a nitrogen atmosphere.
[0540] Once it has cooled to 160°C, 25 parts of trimellitic acid are added.
[0541] Then, a mixture of 450 parts of styrene, 200 parts of 2-ethylhexyl acrylate and 30 parts of dicumyl peroxide as a polymerization initiator was dropped at 160° C. over 2 hours. After the dropwise addition was completed, the temperature was raised to 200° C. and the reaction mixture was reacted for 3 hours to obtain a non-crystalline resin A12 having a softening point of 115° C.
[0542] The peak molecular weight of the obtained non-crystalline resin A12 obtained by GPC was 9000. The glass transition temperature was 60° C. and the acid value was 5 mg KOH / g.
[0543] Production Example of Non-Crystalline Resin A13
[0544] Low molecular weight polypropylene (Sanyo Chemical Industries, Ltd., Viscol 660P): 10.0 parts
[0545] (0.02 mol; 2.4 mol% relative to the total molar number of component monomers)
[0546] Xylene: 25.0 parts
[0547] These materials were weighed into a reaction vessel equipped with a cooling tube, a stirrer, a nitrogen inlet tube and a thermocouple. The flask was purged with nitrogen and the temperature was gradually raised to 175°C while stirring.
[0548]
[0549]
[0550] These materials were then added dropwise over 2.5 hours, and the mixture was stirred for another 40 minutes. The solvent was then distilled off to obtain a non-crystalline resin A13 comprising a styrene acrylic polymer grafted to a polyolefin.
[0551] The peak molecular weight of the obtained non-crystalline resin A13 obtained by GPC was 11000. The glass transition temperature was 62° C. and the acid value was 0.4 mg KOH / g.
[0552] [Table 1-1]
[0553]
[0554] The abbreviations in Table 1-1 are defined as follows.
[0555] BPA-PO (2.2): Bisphenol A propylene oxide 2.2 molar adduct
[0556] BPA-EO(2.2): Bisphenol A ethylene oxide 2.2 molar adduct
[0557] EG: Ethylene glycol
[0558] TFA: Terephthalic acid
[0559] TMA: trimellitic acid
[0560] FA: Fumaric acid
[0561] OA: Oxalic acid
[0562] SUA: Succinic Acid
[0563] AA: Adipic acid
[0564] SEA: Sebacic Acid
[0565] DCA: Dodecenylsuccinic anhydride
[0566] [Table 1-2]
[0567]
[0568] The unit of Tg is °C and the unit of acid value is mg KOH / g, and the dielectric constant is pF / m at 2 kHz.
[0569] Production Example of Binder Resin 1
[0570] 32 parts of non-crystalline resin A6 and 68 parts of crystalline resin C1 were mixed and supplied to a twin-screw kneader (Kurimoto, Ltd., S5KRC kneader) at a rate of 52 kg / hour, and 1.0 part of tert-butyl peroxyisopropyl monocarbonate as a radical reaction initiator (c) was supplied at a rate of 0.52 kg / hour and kneaded and extruded at 160°C, 90 rpm for 7 minutes to perform a crosslinking reaction, and then mixed while removing the organic solvent by reducing the pressure from the discharge port to 10 kPa. The mixed product was then cooled to obtain a binder resin 1.
[0571] Production Examples of Binder Resins 2 to 14
[0572] Binder resins 2 to 14 were obtained according to the manufacturing example of the binder resin 1 except that the types and the mixing ratios of the non-crystalline resin and the crystalline resin were changed as shown in Table 2.
[0573] [Table 2]
[0574]
[0575] Preparation Example of Binder Resin 1 Fine Particle Dispersion Liquid
[0576] Toluene: (Wako Pure Chemical) 300 parts
[0577] Binder resin 1: 100 parts
[0578] These materials were weighed, mixed and dissolved at 90°C.
[0579] 5.0 parts of sodium dodecylbenzenesulfonate and 10.0 parts of sodium laurate were separately added to 700 parts of ion-exchanged water, and heated to be dissolved at 90°C.
[0580] The toluene solution and the aqueous solution were then mixed and stirred at 7000 rpm using a TK Robomix ultra-high speed stirring device (Primix Corp.). Next, it was emulsified at a pressure of 200 MPa using a high pressure impact dispersion machine (Yoshida Kikai Co., Ltd.). Toluene was then removed using an evaporator, and the concentration was adjusted with ion exchange water to obtain a 20 mass % aqueous dispersion of binder resin 1 fine particles (binder resin 1 fine particle dispersion).
[0581] The 50% particle diameter (D50) based on volume distribution of the fine particles of the binder resin 1 was measured by Nanotrac UPA-EX150 (Nikkiso Co., Ltd.) to find that it was 0.40 μm.
[0582] Production Example of Fine Particle Dispersion Liquid of Binder Resins 2 to 14
[0583] Fine particle dispersions of Binder Resins 2 to 14 were obtained by the same emulsification as in the Production Example of the Fine Particle Dispersion of Binder Resin 1, except that Binder Resin 1 was replaced by Binder Resins 2 to 14.
[0584] Preparation Example of Non-Crystalline Resin A1 Fine Particle Dispersion Liquid
[0585] Tetrahydrofuran: (Wako Pure Chemical) 300 parts
[0586] Non-crystalline resin A1: 100 parts
[0587] Anionic surfactant Neogen RK (DKS Co. Ltd.): 0.5 parts
[0588] The materials were weighed, mixed and dissolved.
[0589] Next, 20.0 parts of 1 mol / liter ammonia water was added and stirred at 4000 rpm with an ultra-high-speed TK Robomix stirrer (Primix Corp.). Then 700 parts of ion-exchanged water was added at a rate of 8 g / min to precipitate non-crystalline resin A1 fine particles. Tetrahydrofuran was then removed with an evaporator, and the concentration was adjusted with ion-exchanged water to obtain an aqueous dispersion of non-crystalline resin A1 fine particles having a concentration of 20% by mass (non-crystalline resin A1 fine particle dispersion).
[0590] The non-crystalline resin A1 fine particle dispersion liquid had a volume-based 50% particle diameter (D50) of 0.13 μm.
[0591] Production Example of Fine Particle Dispersion Liquid of Amorphous Resins A2 to A13
[0592] Fine particle dispersions of non-crystalline resins A2 to A13 were obtained in the same manner as in the production example of the fine particle dispersion of non-crystalline resin A1, except that the non-crystalline resin A1 in the fine particle dispersion of non-crystalline resin A1 was replaced by non-crystalline resins A2 to A13.
[0593] Preparation Example of Fine Particle Dispersion Liquid of Crystalline Resins C1 to C8
[0594] Fine particle dispersions of crystalline resins C1 to C8 were obtained according to the production example of the dispersion of binder resin 1 except that the kind of resin was changed to crystalline resins C1 to C8.
[0595] Preparation Example of Release Agent (Aliphatic Hydrocarbon Compound) Fine Particle Dispersion Liquid
[0596] Aliphatic hydrocarbon compound HNP-51 (Nippon Seiro) 100 parts
[0597] · Anionic surfactant Neogen RK (Daiichi Kogyo) 5 parts
[0598] ·395 parts of ion exchange water
[0599] These materials are weighed accurately, placed in a mixing container with an attached stirrer, heated to 90° C. and then dispersed for 60 minutes by recirculation to a Clearmix W-Motion (M Technique).
[0600] The dispersion conditions are as follows.
[0601]
[0602] After dispersion, it is cooled to 40°C under the conditions of a rotor speed of 1000 r / min, a sieve speed of 0 r / min, and a cooling rate of 10°C / min to obtain an aqueous dispersion (release agent (aliphatic hydrocarbon compound) fine particle dispersion) having a concentration of 20% by mass.
[0603] The particle diameter (D50) of 50% volume-based fine particles of the release agent (aliphatic hydrocarbon compound) measured by Nanotrac UPA-EX150 dynamic light scattering type particle size distribution meter (Nikkiso) was 0.15 μm,
[0604] Production of colorant fine particle dispersion
[0605] ·Colorant 50.0 parts
[0606] (Cyan pigment, Dainichi Seika Pigment Blue 15:3)
[0607] Neogen RK anionic surfactant (Daiichi Kogyo Seiyaku) 7.5 parts
[0608] ·442.5 parts of ion exchange water
[0609] These materials were accurately weighed, mixed, dissolved, and dispersed with a Nanomachine high pressure impact disperser (Yoshida Kikai) for about 1 hour to disperse the colorant and obtain an aqueous dispersion having a colorant fine particle concentration of 10 mass % (colorant fine particle dispersion).
[0610] The 50% volume-based particle diameter (D50) of the colorant fine particles measured by Nanotrac UPA-EX150 dynamic light scattering type particle size distribution meter (Nikkiso) was 0.20 μm.
[0611] Toner Production Example
[0612] Toner Particles 1 Production Example
[0613]
[0614] These materials were placed in a round stainless steel flask and mixed, and then 10 parts of a 10% magnesium sulfate aqueous solution were added. Then, it was dispersed at a speed of 5000 rpm for 10 minutes using an Ultra-Turrax T50 homogenizer (IKA). Then, it was heated to 58° C. in a hot water bath while appropriately adjusting the rotation speed of the stirring blade to stir the mixture.
[0615] The volume average particle size of the formed aggregated particles was appropriately confirmed with Coulter Multisizer III, and once aggregated particles having a volume average particle size of about 6.00 μm were formed, 100 parts of a 5% aqueous solution of ethylenediamine tetrasodium acetate was added, and the mixture was heated to 75° C. while continuing to stir. The temperature was then maintained at 75° C. for 1 hour to fuse the aggregated particles.
[0616] It was then cooled to 50°C and maintained for 3 hours to promote polymer crystallization.
[0617] Next, as a step of removing polyvalent metal ions derived from the coagulant, the mixture was washed with a 5% aqueous solution of sodium ethylenediaminetetraacetate while being maintained at 50°C.
[0618] It was then cooled to 25° C., filtered and solid-liquid separated, and then washed with ion-exchanged water. After washing, it was dried with a vacuum dryer to obtain toner particles 1 having a weight average particle size (D4) of about 6.07 μm.
[0619] Production Examples of Toner Particles 2, 4 to 45, and 51 to 60
[0620] Toner particles 2, 4 to 45, and 51 to 60 were obtained by the same operation as in the toner particle 1 production example, except that the kind and addition amount of the binder resin 1 fine particle dispersion, the kind and addition amount of the crystalline fine particles, the kind and addition amount of the non-crystalline resin fine particles, the kind and addition amount of the aggregating agent, the kind of the removing agent, and the adding temperature of the removing agent were changed as shown in Table 3.
[0621] Toner Particles 3 Production Example
[0622]
[0623] These materials were mixed by a Henschel mixer (FM-75, Nippon Coke & Engineering Co., Ltd.) for 20 s. -1 The mixture was mixed at a rotation speed of 1000 rpm and a rotation time of 5 minutes, and then kneaded at a temperature of 120°C and a discharge temperature of 135°C in a twin screw kneader (PCM-30, Ikegai) set at a screw speed of 200 rpm. The kneaded product was cooled at a cooling rate of 15°C / min and coarsely pulverized in a hammer mill to no more than 1 mm to obtain a pulverized product. The pulverized product was then pulverized with a mechanical pulverizer (T-250, Freund-Turbo Corporation).
[0624] This was then classified using Faculty F-300 (Hosokawa Micron Corporation) to obtain toner particles 3. As for the operating conditions, the classification rotor speed was set to 130 s -1 and the dispersion rotor speed was set to 120 s -1 .
[0625] Production Example of Toner Particles 46
[0626] Toner particles 46 were obtained according to the production example of toner particles 3 except that the type and amount of the binder resin were changed as shown in Table 3.
[0627] Production Example of Toner Particles 47
[0628] Toner particles 47 were obtained according to the production example of toner particles 3 except that the type and amount of the binder resin were changed as shown in Table 3 and the screw speed of the twin-screw mixer was changed to 300 rpm.
[0629] Production Example of Toner Particles 48
[0630] Toner particles 48 were obtained in the same manner as in the production example of toner particles 3 except that the type and amount of the binder resin were changed as shown in Table 3 and the screw speed of the twin-screw mixer was changed to 150 rpm.
[0631] Production Example of Toner Particles 49
[0632] Toner particles 49 were obtained according to the production example of toner particles 3 except that the type and amount of the binder resin were changed as shown in Table 3, the temperature of the twin-screw mixer was changed to 100° C., and the screw speed was changed to 350 rpm.
[0633] Production Example of Toner Particles 50
[0634] Toner particles 50 were obtained according to the production example of toner particles 3 except that the type and amount of the binder resin were changed as shown in Table 3, the temperature of the twin-screw mixer was changed to 140° C., and the screw rotation speed was changed to 100 rpm.
[0635] Toner 1 Production Example
[0636] ·Toner particles 1: 100 parts
[0637] ·Hexamethyldisilazane surface treated large-size silica fine particles (average particle size 130nm): 3 parts
[0638] · Small-sized silica fine particles (average particle size 20 nm) treated with hexamethyldisilazane: 1 part
[0639] These materials were mixed by a FM-10C Henschel mixer (Mitsui Miike Machinery Co., Ltd.) at 30 s. -1 The mixture was mixed for 10 minutes at a rotation speed of 0.02 and a rotation time of 10 minutes to obtain Toner 1.
[0640] The weight average particle size (D4) of Toner 1 was 6.1 μm and the average circularity was 0.975. The physical properties of Toner 1 are shown in Table 4.
[0641] Production Examples of Toners 2 to 60
[0642] Toners 2 to 60 were obtained according to the production example of Toner 1 except that the kind of toner particles was changed as shown in Table 3. The physical properties are shown in Table 4. In Toners 22 to 25, the removal step was adjusted so that the ratio of the monovalent metal element was as shown in Table 4.
[0643] In cross-sectional observation of the obtained toners, a domain-matrix structure composed of a matrix containing the first resin (crystalline resin) and a domain containing the second resin (non-crystalline resin) was observed in Toners 1 to 50 , 52 to 56 , and 58 to 60 .
[0644] In Toners 51 and 57, a domain-matrix structure composed of a matrix containing the second resin and domains containing the first resin was observed.
[0645] [Table 3]
[0646]
[0647]
[0648]
[0649] The abbreviations in Table 3 are defined as follows:
[0650] M: Manufacturing method
[0651] EA: Emulsion Aggregation
[0652] SP: Suspension polymerization
[0653] MK: Melt kneading
[0654] Mg: magnesium sulfate
[0655] Ca: Calcium nitrate
[0656] Zn: Zinc chloride
[0657] Al: Aluminum sulfate
[0658] Fe:Ferric polysulfate
[0659] Na:Sodium EDTA
[0660] Li: Lithium citrate
[0661] K: Potassium citrate
[0662] Temp.: Temperature
[0663] [Table 4]
[0664]
[0665] In the table, X is the content (mass %) of the first resin in the binder resin, and X / Y is the mass ratio of the content X of the first resin to the content Y of the second resin in the binder resin. Mu1 represents the polyvalent metal content [parts], Mon represents the monovalent metal content [parts], and MR represents the monovalent metal ratio [mass %], and the metal content [parts] is the amount relative to 100 parts of the binder resin.
[0666] D4 is the weight average particle size. DM65 represents the complex elastic modulus at 65° C., and DM85 represents the complex elastic modulus at 85° C. DD represents the domain diameter, and the domain diameter is the number average diameter of the domains.
[0667] U1 represents the content ratio of the first monomer unit in the first resin. M / U represents (parts by mass of the polyvalent metal element in the toner relative to 100 parts by mass of the binder resin)×10000 / (content ratio of the first monomer unit in the first resin). AC represents the average circularity.
[0668] Production Example of Magnetic Carrier 1
[0669] Magnetite 1 with a number average particle size of 0.30 μm (magnetization intensity in a magnetic field of 1000 / 4π (kA / m) is 65 Am 2 / kg)
[0670] Magnetite 2 with a number average particle size of 0.50 μm (magnetization intensity in a magnetic field of 1000 / 4π (kA / m) is 65 Am 2 / kg)
[0671] 4.0 parts of a silane compound (3-(2-aminoethylaminopropyl)trimethoxysilane) was added to 100 parts of each of the above materials, and the mixture was mixed and stirred at a high speed at 100° C. or higher in a container to treat the respective fine particles.
[0672]
[0673] 100 parts of these materials, 5 parts of 28 mass % ammonia aqueous solution and 20 parts of water were placed in a flask, stirred and mixed while raising the temperature to 85° C. over 30 minutes and maintaining for 3 hours to perform polymerization reaction, and the resulting phenolic resin was hardened.
[0674] The hardened phenolic resin was then cooled to 30°C, water was added, the supernatant was removed, and the precipitate was washed with water and air-dried. It was then dried at 60°C under reduced pressure (5 mmHg or less) to obtain a magnetically dispersed spherical magnetic carrier. The volume-based 50% particle size (D50) was 34.2 μm.
[0675] Production Example of Two-Component Developer 1
[0676] Two-component developer 1 was obtained by mixing 92.0 parts of magnetic carrier 1 and 8.0 parts of toner 1 in a V-type mixer (V-20, Seishin Enterprise Co., Ltd.).
[0677] Production Example of Two-Component Developers 2 to 60
[0678] Except that the toner was changed as shown in Table 5, two-component developers 2 to 60 were obtained according to the manufacturing example of two-component developer 1.
[0679] [Table 5]
[0680]
[0681]
[0682] Toner Evaluation Method
[0683] Evaluation method of low temperature fixability
[0684] Paper: GFC-081(81.0g / m 2 )(Sold by Canon Marketing Japan Inc.)
[0685] Toner loading on paper: 0.50mg / cm 2 (Adjusted by the DC voltage VDC of the developer bearing member, the charging voltage VD of the electrostatic latent image bearing member and the laser power)
[0686] Evaluation image: 2cm x 5cm image in the center of A4 paper
[0687] Test environment: 15°C, 10%RH low temperature and low humidity environment (hereinafter referred to as "L / L")
[0688] Fixing temperature: 130℃
[0689] Processing speed: 377mm / sec
[0690] The evaluation image was output and the low-temperature fixability was evaluated. The image density reduction rate was used as an evaluation standard for the low-temperature fixability.
[0691] For the image density reduction rate, the image density at the center of the image was first measured using an X-Rite color reflection densitometer (500 series, X-Rite Inc.). 2 ), the fixed image on the portion where the image density had been measured was rubbed with Silbon paper (5 reciprocations) under a load of 1.5 % and the image density was measured again.
[0692] Then, the image density reduction rate after rubbing was calculated by the following formula. The obtained image density reduction rate was evaluated according to the following criteria. Grade D or above indicates that the effect of the present invention has been obtained. The evaluation results are shown in Table 6.
[0693] Image density reduction rate =
[0694] (Image density before rubbing - Image density after rubbing) / Image density before rubbing × 100
[0695] (Evaluation Criteria)
[0696] AA: Image density reduction rate is less than 3.0%
[0697] A: Image density reduction rate 3.0% or more and less than 5.0%
[0698] BB: Image density reduction rate 5.0% or more and less than 10.0%
[0699] B: Image density reduction rate 10.0% or more and less than 15.0%
[0700] CC: Image density reduction rate 15.0% or more and less than 20.0%
[0701] C: Image density reduction rate 20.0% or more and less than 25.0%
[0702] D: Image density reduction rate 25.0% or more and less than 30.0%
[0703] E: Image density reduction rate 30.0% or more
[0704] Evaluation method of hot fouling resistance (HO)
[0705] Using a modified Canon imagePRESS C800 full-color copier as an unfixed image forming unit, the above two-component developer was placed in a cyan station developing device and evaluated.
[0706] Use GFC-081 ordinary copy paper (A4, basis weight 81.4g / m 2 , Canon Marketing Japan Inc.) as the evaluation paper. An unfixed toner image (toner load 0.08 mg / cm) with a length of 2.0 cm and a width of 15.0 cm was formed at a portion 2.0 cm from the top of the paper in the paper feeding direction under a normal temperature and humidity environment (23°C, 60% RH) 2 ).
[0707] The fixing test was carried out using a fixing unit that had been taken out of an image RUNNER ADVANCE C5255 Canon full-color copier and modified so that the fixing temperature could be adjusted. In a normal temperature and humidity environment (23°C, 5% RH), the process speed was set to 265 mm / s, and the temperature was raised from 160°C to 210°C in 5°C increments, and a fixed image was obtained from a previous unfixed image at each temperature. The heat offset resistance of the resulting fixed image was then evaluated.
[0708] The hot offset in the fixed image was visually evaluated and judged according to the following criteria. A grade of D or higher indicates that the effect of the present invention has been obtained. The evaluation results are shown in Table 6.
[0709] (Evaluation Criteria)
[0710] AA: No thermal fouling even at 210°C
[0711] A: Thermal fouling at 205°C
[0712] BB: Thermal fouling at 200°C
[0713] B: Thermal fouling at 195°C
[0714] CC: Thermal fouling at 190°C
[0715] C: Thermal fouling at 180°C or above and less than 190°C
[0716] D: Thermal fouling at 170°C or above and less than 180°C
[0717] E: Thermal fouling below 170°C
[0718] Evaluation method of fixing separation
[0719] Using the modified copying machine, a photosensitive resin having a thickness of 0.60 mg / cm was formed without fixing. 2 A full-page solid image with a toner loading of 1.5475 mm, leaving a 3.0 mm white border at the top edge of the page.
[0720] The unfixed image was then fixed using a modified fixing unit at a process speed of 450 mm / sec.
[0721] To evaluate the fixing separation property, the fixing temperature was lowered from 200° C. in increments of 5° C., and the temperature at which winding occurred plus 5° C. was taken as the minimum fixing temperature. The test environment was a high temperature and high humidity environment (30° C. / 80% RH).
[0722] A4 size CS-680 paper (Canon, 60g / m 2 ) is used as a transfer material for fixing an image. The evaluation criteria are as follows. Grade D or above means that the effect of the present invention has been obtained. The evaluation results are shown in Table 6.
[0723] (Evaluation Criteria)
[0724] AA: Minimum fixing temperature is less than 160°C
[0725] A: The minimum fixing temperature is 160°C
[0726] BB: Minimum fixing temperature is 165°C
[0727] B: Minimum fixing temperature is 170℃
[0728] CC: Minimum fixing temperature is 175℃
[0729] C: Minimum fixing temperature is 180℃
[0730] D: Minimum fixing temperature is 185°C
[0731] E: Minimum fixing temperature is at least 190°C
[0732] Evaluation method of charge retention characteristics in high temperature and high humidity environments
[0733] The toner on the electrostatic latent image bearing member is collected by suction using a metal cylindrical pipe and a cylindrical filter to measure the triboelectric charge amount of the toner.
[0734] Specifically, the friction charge amount of the toner on the electrostatic latent image bearing member is measured with a Faraday cage, which is a coaxial double cylinder in which the inner cylinder and the outer cylinder are insulated from each other. If a charged body with a charge amount Q is placed in the inner cylinder, electrostatic induction makes it seem as if there is a metal cylinder with a charge amount Q. The induced charge amount is measured with an electrometer (Keithley 6517A, Keithley), and the charge amount Q (mC) is divided by the mass M (kg) of the toner in the inner cylinder (Q / M), and is regarded as the friction charge amount of the toner.
[0735] Toner triboelectric charge (mC / kg) = Q / M
[0736] An image for evaluation is first formed on an electrostatic latent image bearing member, and then before it can be transferred to an intermediate transfer member, the rotation of the electrostatic latent image bearing member is stopped, and the toner on the electrostatic latent image bearing member is collected by suction with a metal cylindrical pipe and a cylindrical filter, and the "initial Q / M" is measured.
[0737] Next, the evaluation unit was left for two weeks with the developing device still installed in the high temperature and high humidity environment (H / H), the same operation as before was performed, and the charge amount Q / M (mC / kg) per unit mass on the electrostatic latent image bearing member after the leaving was measured. The initial Q / M per unit mass on the electrostatic latent image bearing member was taken as 100%, and the maintenance rate of Q / M per unit mass on the electrostatic latent image bearing member after the leaving was calculated and evaluated according to the following criteria ([Q / M after leaving] / [initial Q / M]×100).
[0738] The evaluation results are shown in Table 6.
[0739] (Evaluation Criteria)
[0740] A: The maintenance rate is more than 95%
[0741] B: The maintenance rate is 90% or more and less than 95%
[0742] C: The maintenance rate is 85% or more and less than 90%
[0743] D: The maintenance rate is 80% or more and less than 85%
[0744] E: The maintenance rate is less than 80%
[0745] Evaluation method for fogging of non-image areas
[0746] Using a Canon imagePress C10000 VP full-color copier as an image forming apparatus, the two-component developer 1 was placed in the developing device of the cyan station and evaluated.
[0747] The evaluation environment was high temperature and high humidity (30°C, 80% RH), and GFC-081 flat copy paper (A4, basis weight 81.4 g / m 2 , sold by Canon Marketing Japan Inc.) as evaluation paper.
[0748] 50,000 sheets were output at an image printing rate of 20% and fogging of the white portion was measured before and after the durability test.
[0749] The average reflection density Dr (%) of the evaluation paper before image output was measured using a reflectometer (Reflectometer Model TC-6DS, Tokyo Denshoku Co., Ltd.).
[0750] The reflection density Ds (%) of the 00H image portion (white portion) after the durability test (50,000th sheet) was also measured. The value of Ds after the durability test (50,000th sheet) minus Dr was taken as fogging (%) and evaluated according to the following criteria. Grade D or above means that the effect of the present invention has been obtained. The evaluation results are shown in Table 6.
[0751] (Evaluation Criteria)
[0752] A: less than 0.5%
[0753] B: 0.5% or more and less than 1.0%
[0754] C: 1.0% or more and less than 2.0%
[0755] D: 2.0% or more and less than 3.0%
[0756] E: 3.0% or more
[0757] Examples 1 to 50
[0758] The above evaluation was performed using Toners 1 to 50 (two-component developers 1 to 50).
[0759] Comparative Examples 1 to 10
[0760] The above evaluation was performed using Toners 51 to 60 (two-component developers 51 to 60).
[0761] [Table 6]
[0762]
[0763]
[0764] The abbreviations in Table 6 are defined as follows.
[0765] DDR: Concentration reduction rate
[0766] HOT: HO generation temperature
[0767] MFT: Minimum fixing temperature
[0768] RR: maintenance rate
[0769] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments. The scope of the following claims is to be accorded the broadest and most consistent description so as to encompass all such modifications and equivalent structures and functions.
Claims
1. A toner comprising toner particles, wherein the toner particles contain: A binder resin comprising a first resin and a second resin, characterized in that The first resin is a crystalline resin, The second resin is a non-crystalline resin, The first resin has a first monomer unit represented by the following formula (1), The content ratio of the first monomer unit in the first resin is 30.0 mass % to 99.9 mass %, The acid value of the first resin is 0.1 mg KOH / g to 30 mg KOH / g, The acid value of the second resin is 0.5 mg KOH / g to 40 mg KOH / g, A domain-matrix structure formed by a matrix containing the first resin and a domain containing the second resin appears in cross-sectional observation of the toner, The toner particles further contain a polyvalent metal element, The polyvalent metal element is at least one metal element selected from the group consisting of Mg, Ca, Al, Fe and Zn, The total content of the polyvalent metal element is 0.0025 parts by mass to 3.0000 parts by mass relative to 100 parts by mass of the binder resin, The second resin is a polyester resin, and The polyester resin has a polycondensation structure of dodecenylsuccinic acid or its anhydride: In formula (1), R Z1 represents a hydrogen atom or a methyl group, and R represents C 18-36 alkyl. 2 . The toner according to claim 1 , wherein a mass ratio X / Y of a content X of the first resin in the binder resin to a content Y of the second resin in the binder resin is 0.2 to 2.
5. 3 . The toner according to claim 1 , wherein a number average diameter of the domains in cross-sectional observation of the toner is from 0.1 μm to 2.0 μm. 4 . The toner according to claim 1 , wherein a total content of the polyvalent metal element in the toner is 0.0025 parts by mass to 0.0500 parts by mass relative to 100 parts by mass of the binder resin. 5 . The toner according to claim 1 , wherein the polyester resin has a polycondensation structure of a carboxylic acid component other than a polycondensation structure of dodecenylsuccinic acid or its anhydride.
6. The toner according to claim 1 or 2, wherein in gel permeation chromatography measurement of tetrahydrofuran soluble matter of the toner, when Mw(A) is a weight average molecular weight and Mn(A) is a number average molecular weight, Mw(A) is 25000 to 60000, and Mw(A) / Mn(A) is 5 to 10. 7 . The toner according to claim 1 , wherein the content of the first resin in the binder resin is at least 30.0% by mass.
8. The toner according to claim 1 or 2, wherein The toner particles contain a monovalent metal element, and The monovalent metal element is at least one selected from the group consisting of Na, Li, and K. 9 . The toner according to claim 8 , wherein a content of the monovalent metal element is 45% by mass to 90% by mass based on a total content of the polyvalent metal element and the monovalent metal element.
10. The toner according to claim 1 or 2, wherein The complex elastic modulus of the toner at 65° C. is 1.00×10 7 Pa to 5.00×10 7 Pa, and The complex elastic modulus of the toner at 85° C. is not more than 1.00×10 6 Pa.
11. The toner according to claim 1 or 2, wherein The binder resin further comprises a third resin, and The third resin includes a resin connecting the first resin and the second resin. 12 . The toner according to claim 1 , wherein the second resin is at least one selected from the group consisting of a vinyl resin, a polyester resin, and a hybrid resin including a vinyl resin bonded to a polyester resin.
13. The toner according to claim 1 or 2, wherein The first resin has a second monomer unit that is different from the first monomer unit and is at least one selected from the group consisting of a monomer unit represented by the following formula (2) and a monomer unit represented by the following formula (3), and When SP 21 is the SP value (J / cm 3 ) 0.5 When the SP 21 At least 21.00: In formula (2), X is a single bond or C 1-6 Alkylene, R 1 For -C≡N, -C(=O)NHR 10 , where R 10 Represents a hydrogen atom or C 1-4 alkyl, Hydroxyl, -COOR 11 , where R 11 Represents C 1-6 Alkyl or C 1-6 Hydroxyalkyl, -NH-C(=O)-N(R 13 )2, where two R 13 Each independently represents a hydrogen atom or a C 1-6 alkyl, -COO(CH2)2NHCOOR 14 , where R 14 Represents C 1-4 Alkyl, or -COO(CH2)2-NH-C(=O)-N(R 15 )2, where two R 15 Each independently represents a hydrogen atom or a C 1-6 Alkyl, and R 2 represents a hydrogen atom or a methyl group; and In formula (3), R 3 Represents C 1-4 Alkyl and R 4 represents a hydrogen atom or a methyl group.
14. The toner according to claim 1 or 2, wherein the toner is a non-magnetic toner. 15 . The toner according to claim 1 , wherein the toner particles contain a polyvalent metal element in a non-phase-separated state.
16. A method for producing a toner according to any one of claims 1 to 15, characterized in that: The method comprises: a step of preparing a dispersion of fine resin particles containing a binder resin; a step of adding a coagulant to the resin fine particle dispersion to form aggregated particles; and a step of heating and fusing the aggregated particles to obtain a dispersion containing toner particles, wherein The binder resin includes a first resin and a second resin, The first resin is a crystalline resin, The second resin is a non-crystalline resin, The first resin has a first monomer unit represented by the following formula (1), The content ratio of the first monomer unit in the first resin is 30.0 mass % to 99.9 mass %, The acid value of the first resin is 0.1 mg KOH / g to 30 mg KOH / g, The acid value of the second resin is 0.5 mg KOH / g to 40 mg KOH / g, A domain-matrix structure formed by a matrix containing the first resin and a domain containing the second resin appears in cross-sectional observation of the toner, The toner particles further contain a polyvalent metal element, The polyvalent metal element is at least one metal element selected from the group consisting of Mg, Ca, Al, Fe and Zn, and The total content of the polyvalent metal element is 0.0025 parts by mass to 3.0000 parts by mass relative to 100 parts by mass of the binder resin: In formula (1), R Z1 represents a hydrogen atom or a methyl group, and R represents C 18-36 alkyl. 17 . The method for producing toner according to claim 16 , wherein the aggregating agent is a metal salt including at least one metal element selected from the group consisting of Mg, Ca, Al, Fe, and Zn.
18. The method for producing a toner according to claim 16 or 17, comprising the step of adding a chelate compound having a chelate ability for metal ions to a dispersion containing the toner particles and removing at least a part of the polyvalent metal element, thereby adjusting the content of the polyvalent metal element.
Citation Information
Patent Citations
Toner
JP2014130243A
Toner binder and toner
WO2019073731A1
Toner binder
JP2019211763A
